Zeolite structures synthesized using mixtures of organic structure directing agents
Patent Information
- Application Number
- CN202180006317.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-02-09
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2041-02-09
Smart Images

Figure CN115210181B_ABST
Abstract
Description
[0001] Cross-references to related applications
[0002] This application claims the full priority interest of U.S. Provisional Application No. 62 / 916992, filed on October 18, 2019. Technical Field
[0003] This disclosure relates to methods for preparing zeolites, catalyst compositions comprising such zeolites, and catalyst articles and systems using such catalyst compositions. Background Technology
[0004] Various treatment methods have been used to treat NO-containing substances. x A mixture of gases is used to reduce air pollution. One type of treatment involves the catalytic reduction of nitrogen oxides. Two processes exist: (1) a non-selective reduction process, in which carbon monoxide, hydrogen, or hydrocarbons are used as reducing agents; and (2) a selective reduction process, in which ammonia or ammonia precursors are used as reducing agents. In the selective reduction process, a high degree of nitrogen oxide removal can be achieved using a small amount of reducing agent, resulting in the formation of nitrogen gas and vapor primarily according to the following equation:
[0005] 4NO + 4NH₃ + O₂ → 4N₂ + 6H₂O (Standard SCR reaction)
[0006] 2NO₂ + 4NH₃ → 3N₂ + 6H₂O (slow SCR reaction)
[0007] NO + NO₂ + 2NH₃ → 2N₂ + 3H₂O (Fast SCR reaction)
[0008] Ideally, the catalyst used in the SCR process should be able to maintain good catalytic activity under hydrothermal conditions and over a wide range of operating temperatures (e.g., 200°C to 600°C or higher). SCR catalysts are typically used under hydrothermal conditions, for example, during the regeneration of fly ash filters, which are components in exhaust gas treatment systems used to remove particulate matter.
[0009] Current catalysts used in SCR methods include molecular sieves, such as zeolites, that exchange ions with catalytic metal ions, such as iron or copper. Metal-promoted zeolite catalysts (including iron-promoted and copper-promoted zeolite catalysts, as well as others) are known for the selective catalytic reduction of nitrogen oxides with ammonia. In particular, for example, copper-exchange microporous zeolites with a chalcogenide (CHA) and AEI framework are used for the selective catalytic reduction (SCR) of NO using ammonia or a secondary ammonia source. x Catalyst.
[0010] Increasingly stringent emission regulations have spurred the need to develop improved NO management techniques. x The ability to manage NO emissions, particularly under lean, low engine exhaust temperature conditions.x SCR catalysts that can effectively and efficiently reduce NO emissions from exhaust gases while also exhibiting sufficient high-temperature thermal stability are needed. There is a demand for zeolite materials with customized adsorption and catalytic functions, as well as methods for preparing microporous zeolites (e.g., zeolites with a CHA framework), which are efficient and low-cost, but also provide materials with suitable properties, for example, for SCR catalysis. In particular, there is a continued need in the art for effective and efficient reduction of NO from exhaust gases. x SCR catalyst emissions.
[0011] The catalytic performance of zeolites is determined not only by their framework connectivity but also by the microscopic atomic arrangement of the framework aluminum (Al) atoms that generate catalytically active sites. Specifically, the distribution of aluminum in zeolites and the availability of extra-framework metal ions (e.g., Cu) that can exchange onto the zeolite... 2+ (CuOH) + The number and structure of Cu sites in zeolites are related to their catalytic activity. The density and distribution of catalytically active Cu sites in zeolites depend on the sites and proximity of aluminum atoms in the zeolite framework. Increasing the proportion and density of useful Cu in zeolites will help improve their catalytic performance without changing the silica-to-alumina ratio (SAR) of the products.
[0012] Recent reports indicate that TMAda was bound in the CHA cage during synthesis. + and Na + Cations, therefore, can be addressed by using inorganic cations (e.g., Na+). + Trimethyladamantylammonium cation (TMAda) is used as an organic structure-directing agent (OSDA) to control the Al distribution in CHA zeolite, and TMAda is used in the synthetic gel. + and Na + The relative proportions can be used to control the degree of Al pairing in zeolite products. (See Gounder and Di Iorio, Chem. Mater., 2016, 28(7), 2236-2247).
[0013] Despite these advances, there remains a great need in the field for synthetic procedures that can control, for example, the sites and proximity of aluminum in zeolite materials by manipulating the type and amount of structure-directing agents used in the synthetic gels, thereby providing zeolite materials with customized adsorption and catalytic functions. Summary of the Invention
[0014] This disclosure generally describes the use of a combination of two organic structure-directing agents (OSDAs) with different structures to template zeolite synthesis, thereby enabling control over the zeolite framework structure and the aluminum distribution in the product zeolite.
[0015] Surprisingly, according to this disclosure, it has been found that the use of certain combinations of mono- and bis-quaternary ammonium ion organic structure directing agents (OSDA) in zeolite synthesis gels provides zeolites with a CHA crystal framework structure, in which the Al sites and pairings in the zeolite product are altered, as evidenced by the difference in balanced Cu absorption when compared with CHA zeolites synthesized with a single mono-quaternary ammonium ion organic structure directing agent.
[0016] Therefore, in one aspect, this disclosure provides a method for synthesizing small-pore zeolite, the method comprising preparing a mixture of water, an aluminum source, a silicon source, a first organic structure directing agent source, and a second organic structure directing agent source to form a synthetic gel; and subjecting the synthetic gel to a crystallization process to crystallize small-pore zeolite; wherein the first organic structure directing agent is a bis-quaternary ammonium cation, and the second organic structure directing agent is a mono-quaternary ammonium cation.
[0017] In another aspect, this disclosure provides a method for synthesizing small-pore zeolites, the method comprising:
[0018] Prepare a mixture of water, an aluminum source, a silicon source, a first organic structure directing agent source, and a second organic structure directing agent source to form a synthetic gel; and
[0019] The synthetic gel is subjected to a crystallization process to crystallize small-pore zeolite;
[0020] The first organic structure directing agent comprises a bis-quaternary ammonium cation, a derivative of a bis-quaternary ammonium cation, or a combination thereof, and the second organic structure directing agent comprises a mono-quaternary ammonium cation, a derivative of a mono-quaternary ammonium cation, or a combination thereof.
[0021] In some embodiments, the microporous zeolite is a cage-like structure, wherein the diameter of the largest possible included sphere in the cage-like structure is from approximately to approximately
[0022] In some embodiments, the bisquaternary ammonium cation comprises about 8 to about 20 carbon atoms. In some embodiments, each nitrogen atom of the bisquaternary ammonium cation carries four substituents, wherein each substituent is independently selected from the group consisting of alkyl, alkenyl, aryl, aralkyl, and combinations thereof. In some embodiments, the bisquaternary ammonium cation has a structure represented by Formula I:
[0023]
[0024] in:
[0025] Substituents R1, R2, and R3 are each methyl or ethyl; or optionally, two R3 groups are linked to form -(CH2). n-bridge, where n is an integer from 1 to 3; and
[0026] X is selected from the group consisting of: alkyl, cycloalkyl, alkenyl, aryl, aralkyl and combinations thereof.
[0027] In some embodiments, the bisquaternary ammonium cation is selected from the group consisting of: N1,N1,N1,N3,N3,N3-hexaethylpropane-1,3-diammonium, N1,N1,N1,N4,N4,N4-hexamethylbutane-1,4-diammonium, N1,N1,N1,N4,N4,N4-hexaethylbutane-1,4-diammonium, (E)-N1,N1,N1,N4,N4,N4-hexamethylbut-2-ene-1,4-diammonium, N1,N1,N1,N5,N5,N5-hexamethylpentane-1,5-diammonium, ( E)-N1,N1,N1,N5,N5,N5-Hexamethylpent-2-ene-1,5-diammonium, N1,N1,N1,N6,N6,N6-Hexamethylhexane-1,6-diammonium, (E)-N1,N1,N1,N6,N6,N6-Hexamethylhexane-2-ene-1,6-diammonium, (2E,4E)-N1,N1,N1,N6,N6,N6-Hexamethylhexane-2,4-diene-1,6-diammonium, N1,N1,N1,N7,N7,N7-Hexamethylheptane-1,7-diammonium, N1,N1,N 1,N8,N8,N8-Hexamethyloctane-1,8-diammonium, N1,N1,N1,N3,N3,N3-Hexamethylcyclohexane-1,3-diammonium, N1,N1,N1,N3,N3,N3-Hexamethylbicyclo[2.2.1]heptane-1,3-diammonium, N1,N1,N1,N3,N3,N3-Hexamethylbenzene-1,3-diammonium, N1,N1,N1,N4,N4,N4-Hexamethylcyclohexane-1,4-diammonium, N1,N1,N1,N4,N4,N4-Hexamethylbicyclo[2.2.1] Heptane-1,4-diammonium, N1,N1,N4,N4,N4-hexamethylbicyclo[2.2.2]octane-1,4-diammonium, N1,N1,N1,N4,N4,N4-hexamethylbenzene-1,4-diammonium, 1,1,4,4-tetramethylpiperazine-1,4-dionium, 1,1,3,3-tetramethylhexahydropyrimidine-1,3-dionium, 1,1'-(1,3-phenylene)bis(N,N,N-trimethylmethaneammonium), 1,1'-(1,4-phenylene)bis(N,N,N-trimethylmethaneammonium), or combinations thereof.
[0028] In some embodiments, the first organic structure directing agent source is a bisquaternary ammonium compound comprising a bisquaternary ammonium cation and an OH- cation. - Cl - and Br -The group consists of a balanced anion. In some embodiments, the first organic structure directing agent source includes a hexamethonium or octamethonium cation. In some embodiments, the first organic structure directing agent source is hexamethonium dihydroxide (HMOH) or octamethonium dihydroxide (OMOH).
[0029] In some embodiments, the monoquaternary ammonium cation comprises about 4 to about 14 carbon atoms. In some embodiments, the nitrogen atom of the monoquaternary ammonium cation carries four substituents, wherein each substituent is independently selected from the group consisting of alkyl, alkenyl, aryl, aralkyl, and combinations thereof. In some embodiments, the monoquaternary ammonium cation has a structure represented by Formula II:
[0030]
[0031] in:
[0032] R1, R2, and R3 are each methyl or ethyl; and
[0033] R4 is selected from the group consisting of: methyl, ethyl, hydroxyethyl, cyclohexyl, aziridine, heptyl, adamantyl, and phenyl;
[0034] Alternatively, R3 and R4 together, or R2, R3 and R4 together, can be linked to form a monocyclic or bicyclic system, which can optionally be substituted by one or more methyl or OH groups.
[0035] In some embodiments, the monoquaternary ammonium cation is selected from the group consisting of tetraethylammonium, 2-hydroxy-N,N,N-trimethylethane-1-ammonium, N,N,N-trimethylcyclohexaneammonium, N,N,N-trimethyladamantane-1-ammonium (TMAda), N,N,N-trimethylbicyclo[2.2.1]heptane-2-ammonium, N,N,N-trimethylphenylammonium, 1,1-dimethylpiperidine-1-onium, 1,1,3,5-tetramethylpiperidine-1-onium, 1-methylquinuclidin-1-ium, 3-hydroxy-1-methylquinuclidin-1-ium, or combinations thereof.
[0036] In some embodiments, the second organic structure directing agent source is a monoquaternary ammonium compound comprising a monoquaternary ammonium cation and an OH- cation. - Cl - and Br -The group consists of a balanced anion. In some embodiments, the second organic structure directing source comprises an N,N,N-trimethyladamantane-1-ammonium cation. In some embodiments, the second organic structure directing source is N,N,N-trimethyladamantane-1-ammonium hydroxide (TMAdaOH). In some embodiments, the first organic structure directing source is HMOH or OMOH, and the second organic structure directing source is TMAdaOH.
[0037] In some embodiments, the molar ratio of the first organic structural directing agent to the second organic structural directing agent is in the range of about 0.001 to about 1000. In some embodiments, the molar ratio of the first organic structural directing agent to the second organic structural directing agent is about 0.1 to about 10. In some embodiments, the molar ratio of the first organic structural directing agent to the second organic structural directing agent is about 0.5 to about 2.
[0038] In some embodiments, the mixture further comprises an inorganic structure-directing agent, wherein the inorganic structure-directing agent is an alkali metal cation or an alkaline earth metal cation. In some embodiments, the alkali metal cation is selected from the group consisting of lithium, sodium, potassium, or cesium.
[0039] In some embodiments, the aluminum source includes one or more of aluminum salts, aluminum metal, alumina, aluminosilicates, or zeolites. In some embodiments, the aluminum source comprises a zeolite having a crystalline framework of FAU, LTA, LTL, MFI, or BEA. In some embodiments, the aluminum source is zeolite Y in the Na+ form.
[0040] In some embodiments, the silicon source is colloidal silica, silanol compounds, alkali metal silicates, pyrolytic silica, amorphous silica, or aluminosilicate. In some embodiments, the silicon source is sodium silicate. In some embodiments, the OH / Si ratio of the synthesized gel is from about 0.03 to about 1.0.
[0041] In some embodiments, the crystallization process includes maintaining the synthetic gel at a temperature of about 90°C to about 250°C. In some embodiments, the crystallization process includes maintaining the synthetic gel at a temperature of about 120°C to about 200°C.
[0042] In some embodiments, the method further includes filtering crystals formed during the heating step.
[0043] In some embodiments, the method further includes calcining the zeolite at a temperature of about 450°C to about 750°C.
[0044] In some embodiments, the small-pore zeolite has a crystalline framework structure type selected from the group consisting of: AEI, AFT, AFX, AFV, AVL, CHA, EAB, ERI, ITW, KFI, LEV, LTA, MER, SAS, SAT, and SAV. In some embodiments, the small-pore zeolite has a crystalline framework structure type selected from the group consisting of: AEI, AFV, AVL, CHA, EAB, ITW, KFI, LEV, LTA, MER, SAS, SAT, and SAV. In some embodiments, the small-pore zeolite has an AEI or CHA crystalline framework structure type. In some embodiments, the small-pore zeolite has a CHA crystalline framework structure type.
[0045] In some embodiments, the microporous zeolite has a silica-alumina ratio (SAR) of about 6 to about 100. In some embodiments, the microporous zeolite has a silica-alumina ratio (SAR) of about 10 to about 30. In some embodiments, the microporous zeolite has an SAR in the range of about 20 to about 30.
[0046] In some embodiments, the small-pore zeolite has a porosity of less than about 75 μm. 2 / g MSA; and at least about 450m 2 / g of ZSA.
[0047] In some embodiments, this porous zeolite exhibits a controlled aluminum distribution compared to zeolites synthesized using only mono-seasonal OSDA, comprising altered aluminum sites and pairing arrangements, characterized by a Cu content greater than 0.25 M. +2 Changing the equilibrium Cu concentration + 2. Absorption.
[0048] In some embodiments, prior to calcination, at least a portion of the pores of the small-pore zeolite are occupied by bis-quaternary ammonium cations, and at least a portion of the pores are occupied by mono-quaternary ammonium cations. In some embodiments, about 1% to about 99% of the pores are occupied by bis-quaternary ammonium cations, and about 99% to about 1% of the pores are occupied by mono-quaternary ammonium cations. In some embodiments, about 60% to about 40% of the pores are occupied by bis-quaternary ammonium cations, and about 40% to about 60% of the pores are occupied by mono-quaternary ammonium cations.
[0049] On the other hand, small-pore zeolites prepared according to the methods disclosed herein are provided.
[0050] In some embodiments, compared to microporous zeolites synthesized using only mono-quaternary OSDA, this microporous zeolite has a controlled aluminum distribution, which includes the arrangement of anionic framework Al centers comprising altered aluminum sites and paired arrangements, characterized by a Cu content greater than 0.25 M. +2 Changing the equilibrium Cu concentration+2 Absorption. In some embodiments, the microporous zeolite comprises a cage-like structure, wherein the diameter of the spheres most likely included in the cage-like structure is from approximately to approximately
[0051] On the other hand, a small-pore zeolite is provided, wherein at least a portion of the pores of the zeolite are occupied by bis-quaternary ammonium cations, and at least a portion of the pores are occupied by mono-quaternary ammonium cations. In some embodiments, the small-pore zeolite comprises a cage-like structure, wherein the diameter of the largest possible sphere in the cage-like structure is from approximately to approximately
[0052] In some embodiments, about 1% to about 99% of the pores are occupied by bis-quaternary ammonium cations, and about 99% to about 1% of the pores are occupied by mono-quaternary ammonium cations. In some embodiments, about 60% to about 40% of the pores are occupied by bis-quaternary ammonium cations, and about 40% to about 60% of the pores are occupied by mono-quaternary ammonium cations.
[0053] In some embodiments, the bisquaternary ammonium cation comprises about 8 to about 20 carbon atoms. In some embodiments, each nitrogen atom of the bisquaternary ammonium cation carries four substituents, wherein each substituent is independently selected from the group consisting of alkyl, alkenyl, aryl, aralkyl, and combinations thereof. In some embodiments, the bisquaternary ammonium cation has a structure represented by Formula I:
[0054]
[0055] in:
[0056] Substituents R1, R2, and R3 are each methyl or ethyl; or optionally, two R3 groups are linked to form -(CH2). n -bridge, where n is an integer from 1 to 3; and
[0057] X is selected from the group consisting of: alkyl, cycloalkyl, alkenyl, aryl, aralkyl and combinations thereof.
[0058] In some embodiments, the quaternary ammonium cation is N1,N1,N1,N3,N3,N3-hexaethylpropane-1,3-diammonium, N1,N1,N1,N4,N4,N4-hexamethylbutane-1,4-diammonium, N1,N1,N1,N4,N4,N4-hexaethylbutane-1,4-diammonium, (E)-N1,N1,N1,N4,N4,N4-hexamethylbut-2-ene-1,4-diammonium, N1,N1,N1,N5,N5,N5-hexamethylpentane-1,5-diammonium, (E)-N1,N1, N1,N5,N5,N5-Hexamethylpent-2-ene-1,5-diammonium, N1,N1,N1,N6,N6,N6-Hexamethylhexane-1,6-diammonium (hexamethylammonium), (E)-N1,N1,N1,N6,N6,N6-Hexamethylhexane-2-ene-1,6-diammonium, (2E,4E)-N1,N1,N1,N6,N6,N6-Hexamethylhexane-2,4-diene-1,6-diammonium, N1,N1,N1,N7,N7,N7-Hexamethylheptane-1,7-diammonium, N1,N1,N1,N8 ,N8,N8-Hexamethyloctane-1,8-diammonium (octamethylammonium), N1,N1,N1,N3,N3,N3-Hexamethylcyclohexane-1,3-diammonium, N1,N1,N1,N3,N3,N3-Hexamethylbicyclo[2.2.1]heptane-1,3-diammonium, N1,N1,N1,N3,N3,N3-Hexamethylbenzene-1,3-diammonium, N1,N1,N1,N4,N4,N4-Hexamethylcyclohexane-1,4-diammonium, N1,N1,N1,N4,N4,N4-Hexamethylbicyclo[2.2.1] Heptane-1,4-diammonium, N1,N1,N4,N4,N4-hexamethylbicyclo[2.2.2]octane-1,4-diammonium, N1,N1,N1,N4,N4,N4-hexamethylbenzene-1,4-diammonium, 1,1,4,4-tetramethylpiperazine-1,4-dionium, 1,1,3,3-tetramethylhexahydropyrimidine-1,3-dionium, 1,1'-(1,3-phenylene)bis(N,N,N-trimethylmethaneammonium), 1,1'-(1,4-phenylene)bis(N,N,N-trimethylmethaneammonium), or combinations thereof. In some embodiments, the quaternary ammonium cation is hexamethylammonium or octamethylammonium.
[0059] In some embodiments, the monoquaternary ammonium cation comprises about 4 to about 14 carbon atoms. In some embodiments, the nitrogen atom of the monoquaternary ammonium cation carries four substituents, wherein each substituent is independently selected from the group consisting of alkyl, alkenyl, aryl, aralkyl, and combinations thereof. In some embodiments, the monoquaternary ammonium cation has a structure represented by Formula II:
[0060]
[0061] in:
[0062] R1, R2, and R3 are each methyl or ethyl; and
[0063] R4 is selected from the group consisting of: methyl, ethyl, hydroxyethyl, cyclohexyl, aziridine, heptyl, adamantyl, and phenyl;
[0064] Alternatively, R3 and R4 together, or R2, R3 and R4 together, can be linked to form a monocyclic or bicyclic system, which can optionally be substituted by one or more methyl or OH groups.
[0065] In some embodiments, the monoquaternary ammonium cation is tetraethylammonium, 2-hydroxy-N,N,N-trimethylethane-1-ammonium, N,N,N-trimethylcyclohexaneammonium, N,N,N-trimethyladamantane-1-ammonium (TMAda), N,N,N-trimethylbicyclo[2.2.1]heptane-2-ammonium, N,N,N-trimethylphenylammonium, 1,1-dimethylpiperidine-1-onium, 1,1,3,5-tetramethylpiperidine-1-onium, 1-methylquinuclidin-1-ium, 3-hydroxy-1-methylquinuclidin-1-ium, or a combination thereof. In some embodiments, the monoquaternary ammonium cation is TMAda. In some embodiments, the bisquaternary ammonium cation is hexamethylammonium or octamethylammonium, while the monoquaternary ammonium cation is TMAda.
[0066] In some embodiments, the small-pore zeolite has a crystalline framework structure type selected from the group consisting of: AEI, AFT, AFX, AFV, AVL, CHA, EAB, ERI, ITW, KFI, LEV, LTA, MER, SAS, SAT, and SAV. In some embodiments, the small-pore zeolite has a crystalline framework structure type selected from the group consisting of: AEI, AFV, AVL, CHA, EAB, ITW, KFI, LEV, LTA, MER, SAS, SAT, and SAV. In some embodiments, the small-pore zeolite has an AEI or CHA crystalline framework structure type. In some embodiments, the small-pore zeolite has a CHA crystalline framework structure type.
[0067] In some embodiments, the microporous zeolite has a silica-alumina ratio (SAR) of about 6 to about 100. In some embodiments, the microporous zeolite has a silica-alumina ratio (SAR) of about 10 to about 30. In some embodiments, the microporous zeolite has an SAR in the range of about 20 to about 30.
[0068] In some embodiments, the small-pore zeolite has a porosity of less than about 75 μm. 2 / g MSA; and at least about 450m 2 / g of ZSA.
[0069] On the other hand, an effective method for reducing nitrogen oxides (NOx) in exhaust gas is provided. x The selective catalytic reduction (SCR) catalyst composition comprises a microporous zeolite as disclosed herein, wherein the SCR catalyst is promoted by a promoter metal. In some embodiments, the promoter metal is present in an amount of about 1.0 wt% to about 10 wt% based on the total weight of the SCR catalyst and calculated as a metal oxide. In some embodiments, the promoter metal is present in an amount of about 4 wt% to about 6 wt%. In some embodiments, the promoter metal is selected from iron, copper, and combinations thereof.
[0070] In another aspect, an SCR catalyst article is provided for effectively reducing nitrogen oxides (NOx) from engine exhaust gas. The SCR catalyst article includes a substrate having an SCR catalyst composition as disclosed herein, the substrate being disposed on at least a portion thereof. In some embodiments, the substrate is a honeycomb substrate. In some embodiments, the honeycomb substrate is a flow-through substrate or a wall-flow filter.
[0071] In another aspect, an exhaust gas treatment system is provided, which includes an SCR catalyst article as disclosed herein, located downstream of and in fluid communication with an engine that generates exhaust gas flow.
[0072] In another aspect, a method for treating an exhaust gas stream is provided, the method comprising contacting the exhaust gas stream with an SCR catalyst product or an exhaust gas treatment system, each as disclosed herein.
[0073] These and other features, aspects, and advantages of this disclosure will become apparent from the following detailed description and the accompanying drawings, which will be briefly described below. The invention includes any combination of two, three, four, or more of the embodiments pointed out above, and any combination of two, three, four, or more features or elements set forth in this disclosure, regardless of whether such features or elements are explicitly combined in the specific embodiments described herein. This disclosure is intended to be understood holistically such that, unless the context clearly indicates otherwise, any separable feature or element of the invention in any aspect and embodiment of the invention should be considered as combinable. Other aspects and advantages of the invention will become apparent from the following description. Attached Figure Description
[0074] To provide an understanding of embodiments of the invention, reference is made to the accompanying drawings, which are not necessarily drawn to scale, and wherein reference numerals refer to components of exemplary embodiments of the invention. The drawings are merely exemplary and should not be construed as limiting the invention.
[0075] Figure 1 It can be a perspective view of a honeycomb substrate that may include a catalyst (i.e., selective catalytic reduction catalyst) support coating composition according to the present disclosure;
[0076] Figure 2 This is a cross-sectional view of a portion of the wall-flow filter substrate.
[0077] Figure 3A This is a cross-sectional view of an embodiment of the layered catalyst product disclosed herein;
[0078] Figure 3B This is a cross-sectional view of an embodiment of the partitioned catalyst product disclosed herein;
[0079] Figure 3C This is a cross-sectional view of an embodiment of the layered and partitioned catalyst article of this disclosure;
[0080] Figure 4 This is a schematic diagram of an embodiment of an exhaust gas treatment system using the SCR catalyst product of this disclosure;
[0081] Figure 5 This is the copper exchange isotherm of the embodiments of this disclosure; and
[0082] Figure 6 This is a DRIFTS measurement of TOT bond vibration according to an embodiment of the present disclosure. Detailed Implementation
[0083] Before describing several exemplary embodiments of the present invention, it should be understood that the invention is not limited to the details of the construction or process steps set forth in the following description. The invention can have other embodiments and can be practiced or implemented in various ways. Although the invention herein has been described with reference to specific embodiments, it should be understood that these embodiments are merely illustrative of the principles and applications of the invention. It will be apparent to those skilled in the art that various modifications and changes can be made to the methods and apparatus of the invention without departing from the spirit and scope of the invention. Therefore, it is intended that the invention include modifications and changes within the scope of the appended claims and their equivalents.
[0084] The following definitions are provided for the terms used in this disclosure.
[0085] Throughout this specification, references to "one embodiment," "some embodiments," "one or more embodiments," or simply "embodiment" mean that a particular feature, structure, material, or characteristic described in connection with that embodiment is included in at least one embodiment of the invention. Therefore, phrases appearing in different places throughout this specification, such as "in one or more embodiments," "in some embodiments," "in one embodiment," or "in an embodiment," do not necessarily refer to the same embodiment of the invention. Furthermore, in one or more embodiments, a particular feature, structure, material, or characteristic may be combined in any suitable manner.
[0086] In this paper, the articles “a” and “an” are used to refer to one or more (i.e., at least one) grammatical objects of the articles mentioned.
[0087] Any ranges listed in this article include end values.
[0088] The term “about” as used throughout this specification is used to describe and indicate small fluctuations. For example, the term “about” can mean less than or equal to ±5%, such as less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.2%, less than or equal to ±0.1%, or less than or equal to ±0.05%. Whether explicitly stated or not, all numerical values herein are modified by the term “about.” Values modified by the term “about” naturally include specific values. For example, “about 5.0” must include 5.0.
[0089] AMO x "" refers to a selective ammonia oxidation catalyst, which is a catalyst containing one or more metals (typically Pt, but not limited to) and an SCR catalyst suitable for converting ammonia to nitrogen.
[0090] The terms "catalyst," "catalyst material," "catalyst composition," or "catalytic material" refer to materials that promote a reaction. For the production of catalytic articles, a substrate, as disclosed below, is coated with a catalyst composition. The coating is a "catalytic coating composition" or "catalytic coating." The terms "catalyst composition" and "catalytic coating composition" are synonymous.
[0091] "CSF" refers to a wall-flow catalytic converter. A wall-flow filter consists of alternating inlet and outlet channels, with the inlet channel blocked at the outlet end and the outlet channel blocked at the inlet end. The flue gas carrying dust entering the inlet channel is forced through the filter wall before exiting the outlet channel. In addition to dust filtration and regeneration, CSF can also carry an oxidation catalyst to oxidize CO and HC to CO2 and H2O, or oxidize NO to NO2 to accelerate downstream SCR catalysis or promote the oxidation of dust particles at lower temperatures. When located after an LNT catalyst, CSF can also have H2S oxidation capabilities to suppress H2S emissions during the LNT desulfurization process.
[0092] "DOC" refers to a diesel oxidation catalyst that converts hydrocarbons and carbon monoxide in the exhaust gas of a diesel engine. Typically, a DOC contains one or more platinum group metals, such as palladium and / or platinum; a support material, such as alumina; zeolite for HC storage; and optionally, a promoter and / or stabilizer.
[0093] "LNT" refers to rarefied NO. x The trapping agent contains platinum group metals, cerium dioxide, and other substances suitable for adsorbing NO under dilute conditions. x Catalysts made from alkaline earth metal scavenging materials (e.g., BaO or MgO). Under oxygen-rich conditions, NO... x It is released and reduced to nitrogen.
[0094] The term "NOx" refers to nitrogen oxide compounds, such as NO or NO2.
[0095] The terms “on” and “over” regarding coatings can be used synonymously. The term “directly on” indicates direct contact. In some embodiments, the disclosed article of manufacture is referred to as a coating included “on” a second coating, and such language is intended to cover embodiments with intervening layers where direct contact between the coatings is not required (i.e., “on” is not equivalent to “directly on”).
[0096] As used herein, the term "selective catalytic reduction" (SCR) refers to a catalytic process that uses a nitrogen-containing reducing agent to reduce nitrogen oxides to dinitrogen (N2). As used herein, the terms "nitrogen oxides" or "NO" are used interchangeably. x " " indicates nitrogen oxides.
[0097] “SCRoF” refers to an SCR catalyst composition that is directly coated onto a wall-flow filter.
[0098] As used herein, the term "structure directing agent" refers to a compound present during the crystallization of zeolite and that helps guide the formation of a desired crystal structure (e.g., CHA).
[0099] As used herein, the term "substrate" refers to a monolithic material on which a catalyst composition (i.e., a catalyst coating) is typically coated in the form of a carrier coating. In one or more embodiments, the substrate is a flow-through monolithic or monolithic wall-flow filter. The carrier coating is formed by preparing a slurry containing a specific solids content (e.g., 30-90% by weight) of catalyst in a liquid, then coating the slurry onto the substrate and drying it to provide a carrier coating layer. The reference to "monolithic substrate" refers to a uniform and continuous monolithic structure from inlet to outlet.
[0100] "Carrier coating" has its usual meaning in the art as a thin, adhesive coating of material (e.g., a catalyst) applied to a "substrate," such as a honeycomb flow-through monolithic substrate or filter substrate, which is porous enough to allow the treated airflow to pass through it. As used herein and as described in Heck, Ronald, and Farrauto, Robert, Catalytic Air Pollution Control (New York: Wiley-Interscience, 2002), pp. 18-19, carrier coatings comprise layers of materials of different compositions disposed on the surface of a monolithic substrate or on an underlying carrier coating layer. The substrate may contain one or more carrier coatings, and each carrier coating layer may differ in some way (e.g., it may differ in its physical properties, such as particle size or microcrystalline phase) and / or in its chemocatalytic function.
[0101] Molecular sieves are framework materials that can be used as catalysts, for example, in particulate form in combination with one or more promoter metals. Molecular sieves are typically materials containing tetrahedral sites and exhibiting a substantially uniform pore distribution, forming an extensive three-dimensional network based on oxygen ions, with an average pore size not exceeding 20 angstroms. The aperture is limited by the size of the ring.
[0102] As used herein, the term "zeolite" refers to a specific embodiment of a molecular sieve containing silicon and aluminum atoms. Zeolites are crystalline materials with fairly uniform pore sizes, which, depending on the type of zeolite and the type and number of cations included in the zeolite lattice, have diameters of approximately 3 to [missing value]. Zeolites are understood as aluminosilicates with an open three-dimensional framework structure consisting of T₄ tetrahedra with shared angles, where T is Al or Si. The cations balancing the charge of the anionic framework loosely associate with framework oxygen, and the remaining pore volume is filled with water molecules. The non-framework cations are generally exchangeable, and the water molecules are removable.
[0103] In specific embodiments, the term "aluminosilicate zeolite" may be used to refer to a zeolite framework that excludes phosphorus or other metals substituted in the framework, while the broader term "zeolite" is intended to include both aluminosilicates and aluminophosphates. In some embodiments, the zeolite is an aluminosilicate zeolite. The term "aluminophosphate" refers to another specific embodiment of a zeolite containing aluminum atoms and phosphate atoms. In some embodiments, the zeolite is aluminosilicate phosphate. Aluminosilicate phosphate zeolites contain SiO4 / AlO4 / PO4 tetrahedra and are referred to as "SAPO". Non-limiting examples of SAPO include SAPO-34 and SAPO-44.
[0104] The molar ratio of silica to alumina (SAR) in zeolites is typically 2 or greater. There are no particular limitations on the SAR value of the zeolite used in the disclosed catalyst compositions, although in some embodiments, a specific SAR value associated with the zeolite may affect the SCR performance of the catalyst composition in which it is incorporated (e.g., particularly after aging). In some embodiments, the SAR value of the zeolite is in the range of about 5 to about 100 or about 5 to about 50. In some embodiments, the SAR is about 5 to about 25, and in other embodiments, the SAR is about 10 to about 15.
[0105] Zeolites can be classified using framework topology, which can be used to identify their structure. In some embodiments, this disclosure relates to zeolites having a chalcogenide (CHA) framework. CHA-framework zeolites have an approximate formula: (Ca, Na₂, K₂, Mg)Al₂Si₄O 12• 6H₂O (e.g., hydrated calcium aluminum silicate). DWBreck described three synthetic forms of zeolite CHA framework molecular sieves in “Zeolite Molecular Sieves” (John Wiley & Sons, 1973), which is incorporated herein by reference. The three synthetic forms reported by Breck are: zeolite KG, described in the *Journal of the Chemical Society* (p. 2822 (1956), Barrer et al.); zeolite D, described in British Patent No. 868,846 (1961); and zeolite R, described in U.S. Patent No. 3,030,181, which is incorporated herein by reference. The synthesis of another synthetic form of zeolite CHA framework type SSZ-13 is described in U.S. Patent No. 4,544,538, which is incorporated herein by reference. In a particular embodiment, the CHA framework zeolite is selected from the group consisting of: SSZ-13, SSZ-62, natural chalcogenide, zeolite KG, Linde D, Linde R, LZ-218, LZ-235, LZ-236, ZK-14, SAPO-34, SAPO-44, SAPO-47 and ZYT-6.
[0106] Zeolites contain secondary building units (SBU) and complex building units (CBU), and appear in many different framework structures. Secondary building units contain up to 16 tetrahedral atoms and are achiral. Complex building units do not need to be achiral, nor are they necessarily used to construct the entire framework. The CHA framework has "double 6-ring" (d6r) secondary building units. A d6r secondary building unit has twelve tetrahedral atoms and is created by connecting two "single s6r units," where "6" represents the position of the tetrahedral silicon and aluminum atoms, and the oxygen atom is located between the tetrahedral atoms.
[0107] In some embodiments, the zeolite of the present invention is a pinhole zeolite. As used herein, the term "pinhole" refers to a pore size smaller than approximately [missing information]. For example, approximately The pore openings. The pore size is defined by the largest ring size. Small-pore zeolites contain channels defined by up to eight tetrahedral atoms. The phrase "8-ring" zeolite refers to a zeolite having 8-ring pore openings and double hexagonal (d6r) secondary building units and having a cage-like structure formed by the connection of four rings between the double hexagonal building units. Exemplary small-pore zeolites include framework types ACO, AEI, AEN, AFN, AFT, AFX, ANA, APC, APD, ATT, CDO, CHA, DDR, DFT, EAB, EDI, EPI, ERI, GIS, GOO, IHW, ITE, ITW, LEV, KFI, MER, MON, NSI, OWE, PAU, PHI, RHO, RTH, SAT, SAV, SIV, THO, TSC, UEI, UFI, VNI, YUG, ZON, and mixtures or commensal forms thereof.
[0108] In some cases, the pores of these zeolites open into larger cavities, referred to herein as “cages.” Not wishing to be bound by theory, these cages are considered relevant to catalysis in many systems because they can provide localized volumes within which reactant molecules, and in some cases catalytic atoms, can interact. To provide more quantitative information about cage size compared to the pore systems present in zeolites, the International Zeolite Association-Structure Committee (IZA-SC) database (accessible, e.g., http: / / www.iza-structure.org / databases; incorporated herein by reference) provides the following information: (i) the diameter of the largest possible sphere; and (ii) the diameter of the largest free sphere capable of diffusion along the three crystallographic directions a, b, and c. Comparative information about the size of zeolite cages versus zeolite pores can be obtained by comparing the diameter values of the largest possible sphere with the diameter values of the largest free sphere capable of diffusion within the framework. However, since cages are generally not symmetrical in all directions, these figures cannot always provide a complete description of the cages present in zeolite structures. For example, the AFX framework considers “aft” cages as CBUs, while the CHA framework considers “cha” cages as CBUs. Both skeletal structures have 8-ring openings, and the diameters of the largest spheres they can encompass are very similar (AFX is...). CHA is However, the structures of these two types of cages differ significantly in practice. Nevertheless, referencing the diameter of the largest possible sphere provides a way to distinguish between caged zeolite structures and those containing only channels.
[0109] Unless otherwise indicated, all parts and percentages are by weight. Unless otherwise stated, “weight percentage (wt%)” is based on the whole composition excluding any volatiles, that is, on the dry solids content.
[0110] Unless otherwise stated herein or clearly contradicted by the context, all methods described herein may be performed in any suitable order. Unless otherwise stated, the use of any and all embodiments or exemplary language (e.g., “such”) provided herein is intended only to better illustrate the materials and methods and does not constitute a limitation on the scope. The language in this specification should not be construed as indicating that any unclaimed element is necessary for the practice of the materials and methods of this disclosure.
[0111] All U.S. patent applications, published patent applications, and patents cited in this article are incorporated herein by reference.
[0112] Synthesis of small-pore zeolites
[0113] As described in non-limiting embodiment, the zeolite material disclosed herein is prepared from a reaction mixture (synthetic gel) comprising a first organic structure directing agent source, a second organic structure directing agent source, a silicon source, an aluminum source, and water. Therefore, in one aspect, a method for synthesizing microporous zeolite is provided, comprising mixing water, an aluminum source, a silicon dioxide source, a first organic structure directing agent (OSDA) source, and a second OSDA source to form a synthetic gel, wherein the first OSDA is a bis-quaternary ammonium cation and the second OSDA is a mono-quaternary ammonium cation; and crystallizing the synthetic gel to crystallize the microporous zeolite. Each component is described more fully below.
[0114] Organic structure directing agent
[0115] To prepare small-pore zeolites according to the disclosed method, OSDA, also referred to herein as a “template” or “templating agent,” is used. For example, OSDA is an organic molecule (i.e., carbon-containing) that guides or directs the molecular shape and pattern of the zeolite framework as a scaffold around which zeolite crystals form. After crystal formation, the OSDA is removed from the internal structure of the crystals (e.g., by calcination), leaving a molecularly porous aluminosilicate cage. The specific type of OSDA used can vary. Typically, OSDA is selected from cyclic amines and / or ammonium compounds, such as quaternary ammonium cations with various substituents. Suitable OSDA disclosures are found, for example, “Zeolites and Related Microporous Materials: State of the Art”, Studies of Surface Science and Catalysis, Vol. 84, pp. 29–36; “Novel Materials in Heterogeneous Catalysis” (edited by Baker and Murrell), Chapter 2, pp. 14–24, May 1990, JAMA 2000, 122, pp. 263–273; and U.S. Patent Nos. 4,544,538 and 6,709,644, each incorporated herein by reference.
[0116] Specifically, the method presented herein utilizes two different OSDAs: the first OSDA is a bis-quaternary ammonium cation, and the second OSDA is a mono-quaternary ammonium cation. As used herein, the term "quaternary ammonium cation" refers to an organic molecule containing a nitrogen atom with four substituents, and therefore possessing a positive (cationic) charge. Quaternary ammonium cations react with anions (e.g., halides, e.g., Cl-) - ,Br - I - ), hydrogen sulfate (HSO4) - ) or hydroxide ions (OH) - The ions, referred to herein as “quaternary ammonium salts” or “quaternary ammonium compounds”, dissociate in solution into free quaternary ammonium cations and corresponding anions. As used herein, the term “source” in relation to OSDA refers to a quaternary ammonium compound (e.g., a salt) that dissociates under zeolite synthesis conditions to provide the quaternary ammonium cation activity as a structure-directing agent.
[0117] As used herein, the term "mono-quaternary ammonium" refers to a molecule containing one quaternary ammonium cation as described herein. As used herein, the term "bis-quaternary ammonium" refers to a molecule containing two quaternary ammonium cations as described herein.
[0118] First OSDA
[0119] In some embodiments, the first OSDA is a bisquaternary ammonium cation. In some embodiments, the bisquaternary ammonium cation comprises about 8 to about 20 carbon atoms, for example, about 8, 9, 10, 11, 12, 13, 14, or 15 carbon atoms to about 16, 17, 18, 19, or 20 carbon atoms. The bisquaternary ammonium cation can comprise various structural arrangements, for example, acyclic or cyclic structures. In some embodiments, the bisquaternary ammonium cation is acyclic, meaning that no cyclic system exists. Non-limiting examples of acyclic bisquaternary ammonium cations include N1,N1,N1,N3,N3,N3-hexaethylpropane-1,3-diammonium and N1,N1,N1,N8,N8,N8-hexamethyloctane-1,8-diammonium. In some embodiments, the bisquaternary ammonium cation is cyclic, meaning that the quaternary ammonium groups are attached to two or more of their substituents, or together with two or more of their substituents, form one or more cyclic systems. Non-limiting examples of cyclic quaternary ammonium cations include N1,N1,N1,N4,N4,N4-hexamethylcyclohexane-1,4-diammonium, 1,1,4,4-tetramethylpiperazine-1,4-diammonium, and N1,N1,N1,N4,N4,N4-hexamethylbicyclo[2.2.2]octane-1,4-diammonium.
[0120] In some embodiments, each nitrogen atom of the bisquaternary ammonium cation carries four substituents, wherein each substituent is independently selected from alkyl, cycloalkyl, alkenyl, aryl, aralkyl, and combinations thereof.
[0121] In some embodiments, the bisquaternary ammonium cation has a structure represented by Formula I:
[0122]
[0123] in:
[0124] Substituents R1, R2, and R3 are each methyl or ethyl; or optionally, two R3 groups may be linked to form -(CH2). n -bridge, where n is an integer from 1 to 3; and
[0125] X is selected from the group consisting of: alkyl, cycloalkyl, alkenyl, aryl, aralkyl and combinations thereof.
[0126] In some embodiments, X is an alkyl group. As used herein, the term "alkyl" refers to a straight-chain or branched saturated hydrocarbon having 2 to 8 carbon atoms. Representative C2-C8 alkyl groups include, but are not limited to, ethyl, n-propyl, n-butyl, n-pentyl, and n-hexyl; while branched C2-C8 alkyl groups include, but are not limited to, isopropyl, sec-butyl, isobutyl, tert-butyl, isopentyl, and 2-methylbutyl.
[0127] In some embodiments, X is an alkenyl group. As used herein, the term "alkenyl" refers to a C2-C8 hydrocarbon containing a normal, secondary, or tertiary carbon atom and having at least one unsaturated site, i.e., carbon-carbon, sp. 2 Double bond. Examples include, but are not limited to: ethylene or vinyl, allyl, 1-butenyl, 2-butenyl, isobutenyl, 1-pentenyl, 2-pentenyl, 3-methyl-1-butenyl, 2-methyl-2-butenyl, 2,3-dimethyl-2-butenyl, etc.
[0128] In some embodiments, X is a cycloalkyl group. As used herein, "cycloalkyl" refers to a saturated carbocyclic group, which can be monocyclic or bicyclic, and includes ring systems having 4 to 8 carbon atoms. Examples of monocyclic cycloalkyl groups include cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and cyclooctyl.
[0129] In some embodiments, X is an aryl group. As used herein, "aryl" refers to C6-C 20 A carbocyclic aromatic group. Examples of aryl groups include, but are not limited to, phenyl and naphthyl groups.
[0130] In some embodiments, X is an aralkyl group. As used herein, "aralkyl" refers to an acyclic alkyl group, one of which is bonded to a carbon atom (usually terminal or sp). 3 The hydrogen atom on a carbon atom is replaced by an aryl group. Typical aralkyl groups include, but are not limited to, benzyl, dibenzyl, 2-phenylethan-1-yl, naphthylmethyl, 2-naphthophenylethan-1-yl, naphthylbenzyl, and 2-naphthophenylethan-1-yl. Aralkyl groups contain 6 to 20 carbon atoms; for example, the alkyl portion of an aralkyl group has 1 to 6 carbon atoms and the aryl portion has 5 to 14 carbon atoms.
[0131] It is important to understand that the above radical nomenclature convention refers to diradicals. For example, substituents identified as "alkyl" will require two connection sites, thus including diradicals such as -CH2CH2-, -CH2CH(CH3)CH2-, etc. This radical nomenclature convention clearly indicates that any alkyl, alkenyl, cycloalkyl, aryl, and aralkyl group is a diradical (i.e., alkylene, alkenylene, cycloalkylene, arylene, and arylalkylene, respectively). It should be understood that, unless otherwise stated, diradical substituents can be connected in any configurational orientation.
[0132] Non-limiting examples of bisquaternary ammonium cations according to Formula I include those structures shown in Table 1.
[0133] Table 1.Non-limiting examples of bisquaternary ammonium cations according to Formula I.
[0134]
[0135]
[0136]
[0137] In some embodiments, the bisquaternary ammonium cation has the structure shown in Table 1.
[0138] In some embodiments, the bisquaternary ammonium cation has a structure selected from the group consisting of: N1,N1,N1,N3,N3,N3-hexaethylpropane-1,3-diammonium, N1,N1,N1,N4,N4,N4-hexamethylbutane-1,4-diammonium, N1,N1,N1,N4,N4,N4-hexaethylbutane-1,4-diammonium, (E)-N1,N1,N1,N4,N4,N4-hexamethylbut-2-ene-1,4-diammonium, N1,N1,N1,N5,N5,N5-hexamethylpentane-1,5- Diammonium, (E)-N1,N1,N1,N5,N5,N5-Hexamethylpent-2-ene-1,5-diammonium, N1,N1,N1,N6,N6,N6-Hexamethylhexane-1,6-diammonium, (E)-N1,N1,N1,N6,N6,N6-Hexamethylhexane-2-ene-1,6-diammonium, (2E,4E)-N1,N1,N1,N6,N6,N6-Hexamethylhexane-2,4-diene-1,6-diammonium, N1,N1,N1,N7,N7,N7-Hexamethylheptane-1,7-diammonium, N1,N 1,N1,N8,N8,N8-Hexamethyloctane-1,8-diammonium, N1,N1,N1,N3,N3,N3-Hexamethylcyclohexane-1,3-diammonium, N1,N1,N1,N3,N3,N3-Hexamethylbicyclo[2.2.1]heptane-1,3-diammonium, N1,N1,N1,N3,N3,N3-Hexamethylbenzene-1,3-diammonium, N1,N1,N1,N4,N4,N4-Hexamethylcyclohexane-1,4-diammonium, N1,N1,N1,N4,N4,N4-Hexamethylbicyclo[2.2. [1] Heptane-1,4-diammonium, N1,N1,N4,N4,N4-hexamethylbicyclo[2.2.2]octane-1,4-diammonium, N1,N1,N1,N4,N4,N4-hexamethylbenzene-1,4-diammonium, 1,1,4,4-tetramethylpiperazine-1,4-dionium, 1,1,3,3-tetramethylhexahydropyrimidine-1,3-dionium, 1,1'-(1,3-phenylene)bis(N,N,N-trimethylmethaneammonium), 1,1'-(1,4-phenylene)bis(N,N,N-trimethylmethaneammonium) and combinations thereof.
[0139] In some embodiments, the first OSDA (i.e., bisquaternary ammonium cation) source is a bisquaternary ammonium compound comprising a bisquaternary ammonium cation as described above and a balancing anion. In some embodiments, the balancing anion is selected from the group consisting of OH, Cl, and Br. In some embodiments, the first organic structure directing agent source is N1,N1,N1,N6,N6,N6-hexamethylhexane-1,6-diammonium dihydrogen hydrate (hexamethylammonium dihydrogen hydrate; HMOH) or N1,N1,N1,N8,N8,N8-hexamethyloctane-1,8-diammonium dihydrogen hydrate (octamethylammonium dihydrogen hydrate; OMOH).
[0140] In some embodiments, the first OSDA comprises a derivative of a bisquaternary ammonium cation. The derivative of a bisquaternary ammonium cation includes compounds generated or prepared from a bisquaternary ammonium cation by substituting an atom with another atom or group of atoms, by eliminating an atom or group of atoms, by converting a single bond to a double or triple bond, or by converting a double or triple bond to a single bond. The derivative of a bisquaternary ammonium cation may be intentionally added to the zeolite synthesis mixture, or it may be generated during the synthesis reaction.
[0141] Second OSDA
[0142] In some embodiments, the second OSDA is a monoquaternary ammonium cation. In some embodiments, the monoquaternary ammonium cation comprises about 4 to about 14 carbon atoms, for example, 4, 5, 6, 7, 8, 9, or 10 carbon atoms to 11, 12, 13, or 14 carbon atoms. The monoquaternary ammonium cation may comprise various structural arrangements, such as acyclic or cyclic structures. In some embodiments, the monoquaternary ammonium cation is acyclic. Non-limiting examples of acyclic monoquaternary ammonium cations include tetramethylammonium and tetraethylammonium. In some embodiments, the monoquaternary ammonium cation is cyclic. Non-limiting examples of cyclic monoquaternary ammonium cations include N,N,N-trimethyladamantane-1-ammonium and 1,1-dimethylpiperidin-1-ammonium.
[0143] In some embodiments, the nitrogen atom of the monoquaternary ammonium cation carries four substituents, wherein each substituent is independently selected from the group consisting of alkyl, cycloalkyl, alkenyl, aryl, aralkyl and combinations thereof, each as defined above.
[0144] In some embodiments, the monoquaternary ammonium cation has a structure represented by Formula II:
[0145]
[0146] in:
[0147] R1, R2, and R3 are each methyl or ethyl; and
[0148] R4 is selected from the group consisting of: methyl, ethyl, hydroxyethyl, benzyl, cyclohexyl, aziridine, heptyl, adamantyl, and phenyl;
[0149] Alternatively, R3 and R4 together with the linked nitrogen, or R2, R3 and R4 together with the linked nitrogen, may be linked to form a monocyclic or bicyclic system, which may optionally be substituted with one or more methyl or OH groups.
[0150] In some embodiments, R3 and R4 together with the linked nitrogen form a piperidine ring (i.e., R3 and R4 together are -(CH2)5-). In some embodiments, the piperidine ring is substituted with one or more methyl groups. In some embodiments, the piperidine ring is substituted with methyl groups at the 3- and 5-positions.
[0151] In some embodiments, R2, R3, and R4 together with the linked nitrogen form an aziridine ring. In some embodiments, the aziridine ring is substituted with a hydroxyl group. In some embodiments, the aziridine ring is substituted with a hydroxyl group at the 3-position.
[0152] Non-limiting examples of monoquaternary ammonium cations having the structure of Formula II include those shown in Table 2.
[0153] Table 2. Non-limiting examples of monoquaternary ammonium cations according to Formula II.
[0154]
[0155]
[0156] In some embodiments, the bisquaternary ammonium cation has the structure shown in Table 2.
[0157] In some embodiments, the monoquaternary ammonium cation is selected from the group consisting of tetraethylammonium, 2-hydroxy-N,N,N-trimethylethane-1-ammonium, N,N,N-trimethylcyclohexaneammonium, N,N,N-trimethyladamantane-1-ammonium (TMAda), N,N,N-trimethylbicyclo[2.2.1]heptane-2-ammonium, N,N,N-trimethylphenylammonium, 1,1-dimethylpiperidine-1-onium, 1,1,3,5-tetramethylpiperidine-1-onium, 1-methylquinuclidin-1-ium, 3-hydroxy-1-methylquinuclidin-1-ium, and combinations thereof. In some embodiments, the second organic structure directing agent is N,N,N-trimethyladamantane-1-ammonium (TMAda).
[0158] In some embodiments, the second OSDA (i.e., monoquaternary ammonium cation) source is a monoquaternary ammonium compound comprising a monoquaternary ammonium cation as described above and a balancing anion. In some embodiments, the balancing anion is selected from the group consisting of OH, Cl, and Br. In some embodiments, the second organic structure directing agent source is TMAdaOH.
[0159] In some embodiments, the first organic structure directing agent source is HMOH or OMOH, and the second organic structure directing agent source is TMAdaOH.
[0160] While it has been previously demonstrated that HMOH alone can guide the synthesis of EUO and *MRE framework zeolites, it has not been previously used for the synthesis of CHA framework zeolites. Surprisingly, according to this disclosure, it has been found that the use of HMOH or OMOH in the presence of TMAdaOH leads to the crystallization of pure CHA phase zeolites.
[0161] The amounts of the first and second OSDAs present in the synthetic gel can vary. In some embodiments, the respective amounts of the first and second OSDAs present can be expressed by a molar ratio relative to silicon. In some embodiments, the molar ratio of the first OSDA to silicon is from about 0.01 to about 0.2, for example, from about 0.01, about 0.02, about 0.03, about 0.04, about 0.05, about 0.06, about 0.07, about 0.08, about 0.09 or about 0.1 to about 0.11, about 0.12, about 0.13, about 0.14, about 0.15, about 0.16, about 0.17, about 0.18, about 0.19 or about 0.2. In some embodiments, the molar ratio of the second OSDA to silicon is from about 0.02 to about 0.1, for example, from about 0.02, about 0.03, about 0.04 or about 0.05 to about 0.06, about 0.07, about 0.08, about 0.09 or about 0.1.
[0162] The ratio of the first organic structural directing agent to the second organic structural directing agent can vary. In some embodiments, the molar ratio of the first organic structural directing agent to the second organic structural directing agent is in the range of about 0.001 to about 1000, for example, from about 0.001, about 0.01, about 0.1, about 0.5, or about 1 to about 10, about 20, about 50, about 100, about 500, or about 1000. In some embodiments, the molar ratio of the first organic structural directing agent to the second organic structural directing agent is about 0.1 to about 10. In some embodiments, the molar ratio of the first organic structural directing agent to the second organic structural directing agent is about 0.5 to about 2.0.
[0163] In some embodiments, the second OSDA comprises a derivative of a monoquaternary ammonium cation. A derivative of a monoquaternary ammonium cation includes compounds generated or made from a monoquaternary ammonium cation by substituting an atom with another atom or group of atoms, by eliminating an atom or group of atoms, by converting a single bond to a double or triple bond, or by converting a double or triple bond to a single bond. The derivative of a monoquaternary ammonium cation may be intentionally added to the zeolite synthesis mixture, or it may be generated during the synthesis reaction.
[0164] Inorganic structure directing agent
[0165] In some embodiments, the synthetic gel further comprises an inorganic structure-directing agent (SDA). The inorganic SDA can vary when present, and in some embodiments, it can be an alkali metal or alkaline earth metal cation. In some embodiments, the inorganic SDA is an alkali metal cation, such as lithium, sodium, potassium, or cesium. In some embodiments, the inorganic SDA is sodium or potassium. The source of the inorganic SDA (e.g., an alkali metal cation) can vary. For example, an alkali metal cation (such as Li) + K + or Cs +) It can be added in the form of a hydroxide or as another suitable salt (e.g., sulfate, chloride, nitrate, etc.). In specific embodiments, the sodium or potassium cation source is sodium hydroxide or potassium hydroxide, such as an aqueous solution of sodium hydroxide (NaOH) or potassium oxide (K₂O). In some embodiments, the sodium or potassium cation source is sodium sulfate or potassium sulfate.
[0166] The amount of inorganic structure-directing agent present can vary. Notably, hydroxide ions are the only essential mineralizing agent required in the reaction mixture, and the amount of hydroxide required for gel synthesis can be provided by an organic structure-directing agent source.
[0167] In some embodiments, an alkali metal hydroxide is used as an inorganic SDA and hydroxide ion source, and is provided in a certain amount to ensure that the synthesized gel has a pH within a specific range. For example, in some embodiments, the pH is advantageously alkaline, such as about 12 to about 13.
[0168] Aluminum source
[0169] The aluminum source can be varied. In some embodiments, the aluminum source is non-zeolite. In some embodiments, the aluminum source is amorphous. For example, in some embodiments, the aluminum source can be an amorphous source selected from aluminum salts (e.g., aluminum triisopropoxide or other alkoxides, aluminum hydroxide, aluminum nitrate, aluminum chloride, aluminum phosphate), aluminum metal, amorphous alumina, or amorphous aluminosilicates. In other embodiments, the aluminum source is crystalline, such as crystalline alumina or zeolite.
[0170] In some embodiments, the aluminum source comprises zeolite. The zeolite used as the aluminum source can vary and will include various zeolite materials known in the art, particularly various aluminosilicate zeolites. In some embodiments, the aluminum source comprises a zeolite having a FAU, LTA, LTL, MFI, or BEA crystalline framework. In some embodiments, the aluminum source is Na. + Zeolite Y in form.
[0171] silicon source
[0172] The silicon source can also be varied. In various embodiments, the silicon is provided by one or more of precipitated silica, colloidal silica, silica gel, silicon hydroxide, silanolates, amorphous silica, aluminosilicates, pyrolytic silica, or silicates (such as alkali silicates). In some embodiments, the silicon source is colloidal silica. In some embodiments, the silicon source is an alkali metal silicate. In some embodiments, the silicon source is sodium silicate.
[0173] In some embodiments, the amounts of silicon and aluminum present in the synthetic gel are selected such that the calculated SAR of the starting composition is between about 1 and about 100, for example, in the range of about 2 to 60. In some embodiments, the SAR of the starting composition is in the range of about 10 to about 35. In some embodiments, the SAR of the starting composition is in the range of about 20 to about 30. Those skilled in the art will know that the SAR in the synthesis and the SAR in the final zeolite are not necessarily the same, and will also know how to select the SAR value in the synthesis to obtain the desired SAR in the final zeolite.
[0174] In some embodiments, the OH / Si ratio of the synthesized gel is from about 0.03 to about 1.0, for example from about 0.03, about 0.04, about 0.05, about 0.06, about 0.07, about 0.08, about 0.09, or about 0.1 to about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, or about 1.0.
[0175] mix
[0176] As described above, the method typically involves forming a reaction mixture containing water, an aluminum source, a silicon source, a first organic structure directing agent (OSDA) source, and a second OSDA to form a synthetic gel; and subjecting the synthetic gel to a crystallization process to crystallize zeolite.
[0177] In some embodiments, the method includes mixing a reaction mixture comprising water, an aluminum source, a silicon source, a first organic structure directing agent (OSDA) source, and a second OSDA source to form an aluminosilicate solution, referred herein as a “synthetic gel” or “gel”. Typically, the synthetic gel has a high solids content (e.g., about 15% or more, or about 20% or more).
[0178] The mixing step can be carried out at different temperatures; in some embodiments, mixing is carried out at room temperature. In some embodiments, mixing is carried out at high temperatures (e.g., above room temperature, such as from about 25°C to about 100°C).
[0179] The mixing step can be performed for varying durations. The time period for mixing can range from 1 second to approximately 24 hours. For example, the time period can be from about 1 second to about 1 minute; or from about 1 minute, about 5 minutes, about 10 minutes, or about 15 minutes to about 30 minutes, about 45 minutes, or about 1 hour; or from about 1 hour, about 2 hours, about 3 hours, about 4 hours, about 5 hours, or about 6 hours to about 12 hours or about 24 hours. In some embodiments, the time period is about 2 hours.
[0180] In some embodiments, mixing can be performed in separate, discrete steps. Therefore, in some embodiments, the method includes a first mixing step comprising adding a first OSDA source, a second OSDA source, and an aluminum source to water to form an aluminum-containing aqueous solution and mixing the aqueous solution for a first time period.
[0181] The first time period can range from 1 second to approximately 24 hours. For example, the first time period can range from approximately 1 second to approximately 1 minute; or from approximately 1 minute, approximately 5 minutes, approximately 10 minutes, or approximately 15 minutes to approximately 30 minutes, approximately 45 minutes, or approximately 1 hour; or from approximately 1 hour, approximately 2 hours, approximately 3 hours, approximately 4 hours, approximately 5 hours, or approximately 6 hours to approximately 12 hours or approximately 24 hours. In some embodiments, the first time period is approximately 15 minutes.
[0182] The first mixing step can be carried out at different temperatures; in some embodiments, mixing is carried out at room temperature. In some embodiments, mixing is carried out at high temperatures (e.g., above room temperature, such as from about 25°C to about 100°C).
[0183] In some embodiments, the method includes a second mixing step, which includes adding a silicon source to an aluminum-containing aqueous solution and mixing for a second time period to form a synthetic gel.
[0184] The second time period can range from 1 second to approximately 24 hours. For example, the second time period can be from approximately 1 second to approximately 1 minute; or from approximately 1 minute, approximately 5 minutes, approximately 10 minutes, or approximately 15 minutes to approximately 30 minutes, approximately 45 minutes, or approximately 1 hour; or from approximately 1 hour, approximately 2 hours, approximately 3 hours, approximately 4 hours, approximately 5 hours, or approximately 6 hours to approximately 12 hours or approximately 24 hours. In some embodiments, the second time period is approximately 2 hours.
[0185] The second mixing step can be carried out at different temperatures; in some embodiments, mixing is carried out at room temperature. In some embodiments, mixing is carried out at high temperatures (e.g., above room temperature, such as from about 25°C to about 100°C).
[0186] In some embodiments, the first time period and the second time period are each independently from about 1 second to about 24 hours. In some embodiments, the first time period is from about 5 minutes to about 1 hour. In some embodiments, the second time period is from about 5 minutes to about 1 hour.
[0187] In some embodiments, the first mixing step and the second mixing step are performed at a temperature of about 20°C to about 100°C. In some embodiments, the first mixing step and the second mixing step are performed at a temperature of about 20°C to about 50°C. In some embodiments, the first mixing step and the second mixing step are performed at a temperature of about 20°C to about 30°C.
[0188] crystallization
[0189] After the synthetic gel components are mixed, the synthetic gel then undergoes a crystallization process to crystallize small-pore zeolite. Crystallization conditions are typically selected to promote the formation of a solid precipitate containing zeolite crystals. Typically, the crystallization process involves maintaining the synthetic gel at a high temperature for a period of time. Typically, the reaction mixture as described above is heated while being stirred in a pressure vessel to obtain the desired small-pore zeolite crystal product. In some embodiments, crystallization optionally further includes adding zeolite seed crystals to the synthetic gel to promote the formation of the desired crystal structure. In some embodiments, the seed crystals have a CHA framework. In some embodiments, the seed crystals are calcined CHA zeolite and are Na... + form.
[0190] In some embodiments, the time period can range from about 24 hours to about 6 days. For example, the time period can range from about 24 hours, about 30 hours, or about 36 hours to about 2 days, about 3 days, about 4 days, about 5 days, or about 6 days. In some embodiments, the time period can range from about 30 hours to about 3 days. In some embodiments, the time period is about 3 days. The crystallization process can be carried out at different temperatures; in some embodiments, the crystallization process is carried out at a temperature ranging from about 90°C to about 250°C, for example from about 120°C to about 200°C, or from about 140°C to about 180°C, accompanied by corresponding autogenous pressure. In some embodiments, the first temperature is from about 160°C to about 180°C.
[0191] After cooling and synthesizing the gel, the precipitate containing the zeolite material is filtered off and optionally further processed. Optionally, the product can be centrifuged. Organic additives can be used to aid in the processing and separation of the solid product. The precipitate is filtered off, and the remaining mother liquor is discarded or can be recycled, for example, as disclosed in U.S. Patent Application Publication No. 2015 / 118150 granted to Yang et al., which is incorporated herein by reference. Spray drying is an optional step in the product processing.
[0192] Further processing
[0193] Zeolite products can be heat-treated or calcined in air or nitrogen. Typical calcination temperatures range from approximately 400°C to approximately 850°C (e.g., approximately 450°C to approximately 750°C) over 1 to 10 hours. After initial calcination, the zeolite products are primarily in alkali metal form (e.g., Na). + form).
[0194] The zeolite obtained after calcination can undergo ion exchange to reduce the amount of alkali or to exchange with, for example, ammonium ions. In some embodiments, single or multiple ammonium ion exchanges can be used to generate NH4 from the zeolite. + In this form, it can optionally be further calcined to form H + Form. Ion exchange methods are well known in the prior art and can be applied without departing from the scope of the claims. For example, ion exchange can be achieved by treatment with an aqueous solution of ammonium chloride.
[0195] Zeolite properties
[0196] In some embodiments, the small-pore zeolite obtained by the method of the present invention has a cage-like structure, wherein the maximum diameter of the spheres that may be included in the cage-like structure is approximately to approximately
[0197] In some embodiments, the microporous zeolite crystals produced by crystallization can be from about 50% to about 100% crystallized. In some embodiments, the microporous zeolite crystals produced by crystallization can be from about 80% to about 99% crystallized or from about 90% to about 97% crystallized. The percentage of crystallization can be measured by X-ray diffraction analysis.
[0198] In some embodiments, the small-pore zeolite has a crystalline framework structure selected from the following: AEI, AFT, AFX, AFV, AVL, CHA, EAB, ITW, KFI, LEV, LTA, MER, SAS, SAT, and SAV. In some embodiments, the small-pore zeolite has a crystalline framework selected from the following: AEI, AFV, AVL, CHA, EAB, ITW, KFI, LEV, LTA, MER, SAS, SAT, and SAV. In some embodiments, the small-pore zeolite has an AEI or CHA crystalline framework. In some embodiments, the small-pore zeolite has a CHA crystalline framework.
[0199] In some embodiments, the microporous zeolite product is characterized by a silica to alumina molar ratio (SAR). In one embodiment, the silica to alumina molar ratio of the microporous zeolite is in the range of 6 to 100. In some embodiments, the zeolite product has an SAR of about 10 to about 30. In some embodiments, the microporous zeolite product has an SAR of about 20 to about 30.
[0200] In some embodiments, the small-pore zeolite products are characterized by a relatively low mesopore surface area (MSA) and good catalytic performance due to the zeolite surface area (ZSA). Pore volume and surface area characteristics can be determined by nitrogen adsorption (BET surface area method). In some embodiments, the MSA of the zeolite products is less than about 75 m². 2 / g (e.g., about 25 to about 75 mg) 2 / g) or less than about 25m 2 / g (e.g., about 5 to about 25mg) 2 / g). The ZSA of zeolite products is typically at least about 450m. 2 / g, or at least about 475m 2 / g, or at least about 500m 2 / g, wherein the exemplary ZSA ranges from about 450 to about 600m 2 / g or about 500 to about 600m 2 / g.
[0201] In some embodiments, the small-pore zeolite product is further characterized by relatively low normalized ZSA loss after treatment with NH4F solution, such as by stirring and ultrasonic treatment (35 kHz, 90 W) at 50°C for 20 minutes with 40 wt% NH4F solution at 350 rpm and then drying and calcining at 450°C for 6 hours to reduce the ZSA loss of the small-pore zeolite material. + After processing, the normalized ZSA loss is less than about 60% (or less than about 50%). NH4F treatment was originally developed by Qin et al. [Qin et al., Angew. Chem. Int. Ed. 2016 55, 19049] as a means of imparting mesoporosity, selectively etching zeolite materials at grain boundaries, interfaces between symbiotic crystallites, and other defect-rich regions. Here, this treatment is used as a means of quantifying defect density by measuring the relative etching rate.
[0202] In some embodiments, the microporous zeolite products disclosed herein exhibit a controlled aluminum distribution, comprising the arrangement of anionic framework Al centers. This controlled aluminum distribution can be demonstrated by properties associated with the zeolite material. For example, in some embodiments, the microporous zeolites disclosed herein exhibit altered Al sites and pairings compared to microporous zeolites prepared by processes in which OSDA is a monoquaternary ammonium cation (e.g., N,N,N-trimethylcyclohexaneammonium alone or N,N,N-trimethyladamantane-1-ammonium (TMAda)). In some embodiments, the equilibrium Cu content of microporous zeolites synthesized using only monoquaternary OSDA is significantly improved. +2 Compared to absorption, altered Al sites and pairings may be characterized by altered equilibrium Cu. +2 Absorption. Specifically, in some embodiments, the zeolites disclosed herein exhibit higher Cu content than expected based on their SAR. +2 Absorption. Under ion exchange conditions, when Cu +2 At higher concentrations (e.g., at least about 0.1 M, at least about 0.2 M, at least about 0.25 M, at least about 0.3 M, or at least about 0.4 M Cu), +2 Concentration can exhibit this difference. In some embodiments, this zeolite may be characterized by a higher concentration of Cu compared to synthesized microporous zeolites using TMAdaOH as the sole organic structure directing agent. +2 Changes in equilibrium Cu at concentrations greater than 0.25 M +2 absorb.
[0203] In some embodiments, prior to calcination, at least a portion of the pores of the microporous zeolite are occupied by bis-quaternary ammonium cations, and at least a portion of the pores are occupied by mono-quaternary ammonium cations (i.e., OSDA used to prepare the microporous zeolite), each ammonium cation as described above. In some embodiments, about 1% to about 99% of the pores are occupied by bis-quaternary ammonium cations, and about 99% to about 1% of the pores are occupied by mono-quaternary ammonium cations. In some embodiments, about 60% to about 40% of the pores are occupied by bis-quaternary ammonium cations, and about 40% to about 60% of the pores are occupied by mono-quaternary ammonium cations. In some embodiments, the bis-quaternary ammonium cation comprises about 8 to about 20 carbon atoms. In some embodiments, each nitrogen atom of the bis-quaternary ammonium cation carries four substituents, and each substituent is independently selected from the group consisting of alkyl, alkenyl, aryl, aralkyl, and combinations thereof. In some embodiments, the bis-quaternary ammonium cation has a structure represented by Formula I:
[0204]
[0205] in:
[0206] Substituents R1, R2, and R3 are each methyl or ethyl; or optionally, two R3 groups are linked to form -(CH2). n -bridge, where n is an integer from 1 to 3; and
[0207] X is selected from the group consisting of: alkyl, cycloalkyl, alkenyl, aryl, aralkyl and combinations thereof, wherein alkyl, cycloalkyl, alkenyl, aryl and arylalkyl are each as defined above.
[0208] In some embodiments, the quaternary ammonium cation is N1,N1,N1,N3,N3,N3-hexaethylpropane-1,3-diammonium, N1,N1,N1,N4,N4,N4-hexamethylbutane-1,4-diammonium, N1,N1,N1,N4,N4,N4-hexaethylbutane-1,4-diammonium, (E)-N1,N1,N1,N4,N4,N4-hexamethylbut-2-ene-1,4-diammonium, N1,N1,N1,N5,N5,N5-hexamethylpentane-1,5-diammonium, (E)-N1,N1, N1,N5,N5,N5-Hexamethylpent-2-ene-1,5-diammonium, N1,N1,N1,N6,N6,N6-Hexamethylhexane-1,6-diammonium (hexamethylammonium), (E)-N1,N1,N1,N6,N6,N6-Hexamethylhexane-2-ene-1,6-diammonium, (2E,4E)-N1,N1,N1,N6,N6,N6-Hexamethylhexane-2,4-diene-1,6-diammonium, N1,N1,N1,N7,N7,N7-Hexamethylheptane-1,7-diammonium, N1,N1,N1,N8 ,N8,N8-Hexamethyloctane-1,8-diammonium (octamethylammonium), N1,N1,N1,N3,N3,N3-Hexamethylcyclohexane-1,3-diammonium, N1,N1,N1,N3,N3,N3-Hexamethylbicyclo[2.2.1]heptane-1,3-diammonium, N1,N1,N1,N3,N3,N3-Hexamethylbenzene-1,3-diammonium, N1,N1,N1,N4,N4,N4-Hexamethylcyclohexane-1,4-diammonium, N1,N1,N1,N4,N4,N4-Hexamethylbicyclo[2.2.1] Heptane-1,4-diammonium, N1,N1,N4,N4,N4-hexamethylbicyclo[2.2.2]octane-1,4-diammonium, N1,N1,N1,N4,N4,N4-hexamethylbenzene-1,4-diammonium, 1,1,4,4-tetramethylpiperazine-1,4-dionium, 1,1,3,3-tetramethylhexahydropyrimidine-1,3-dionium, 1,1'-(1,3-phenylene)bis(N,N,N-trimethylmethaneammonium), 1,1'-(1,4-phenylene)bis(N,N,N-trimethylmethaneammonium), or combinations thereof. In some embodiments, the bisquaternary ammonium cation is selected from Table 1. In some embodiments, the bisquaternary ammonium cation is hexamethylammonium or octamethylammonium.
[0209] In some embodiments, the monoquaternary ammonium cation comprises about 4 to about 14 carbon atoms. The nitrogen atom of the monoquaternary ammonium cation carries four substituents, each of which is independently selected from the group consisting of alkyl, alkenyl, aryl, aralkyl, and combinations thereof.
[0210] In some embodiments, the monoquaternary ammonium cation has a structure represented by Formula II:
[0211]
[0212] in:
[0213] R1, R2, and R3 are each methyl or ethyl; and
[0214] R4 is selected from the group consisting of: methyl, ethyl, hydroxyethyl, cyclohexyl, aziridine, heptyl, adamantyl, and phenyl;
[0215] Alternatively, R3 and R4 together, or R2, R3 and R4 together, can be linked to form a monocyclic or bicyclic system, which can optionally be substituted by one or more methyl or OH groups.
[0216] In some embodiments, the monoquaternary ammonium cation is tetraethylammonium, 2-hydroxy-N,N,N-trimethylethane-1-ammonium, N,N,N-trimethylcyclohexaneammonium, N,N,N-trimethyladamantane-1-ammonium (TMAda), N,N,N-trimethylbicyclo[2.2.1]heptane-2-ammonium, N,N,N-trimethylphenylammonium, 1,1-dimethylpiperidine-1-onium, 1,1,3,5-tetramethylpiperidine-1-onium, 1-methylquinuclidin-1-ium, 3-hydroxy-1-methylquinuclidin-1-ium, or a combination thereof. In some embodiments, the monoquaternary ammonium cation is selected from Table 2. In some embodiments, the monoquaternary ammonium cation is TMAda. In some embodiments, the bisquaternary ammonium cation is hexamethylammonium or octamethylammonium, while the monoquaternary ammonium cation is TMAda.
[0217] The microporous zeolites synthesized by the method of the present invention include carbon-nitrogen ratios and C / N ratios in the range of 7 to 15.
[0218] Promoted zeolite
[0219] In some embodiments, the microporous zeolite materials disclosed herein are further treated with a promoter metal to form a metal-promoted zeolite catalyst (e.g., ion-exchanged). As used herein, the term "promoted" refers to a metal component ("promoter metal") intentionally added to the molecular sieve material, as opposed to impurities inherent in the molecular sieve. Thus, a promoter is intentionally added to enhance the activity of the catalyst compared to a catalyst without an intentionally added promoter. Promoter metals actively participate in promoting chemical reactions, such as copper in the conversion of nitrogen oxides, and are therefore often referred to as active metals. To promote the selective catalytic reduction of nitrogen oxides in the presence of ammonia, in one or more embodiments, a suitable metal is independently exchanged into the disclosed zeolite material.
[0220] In some embodiments, the disclosed zeolite is promoted with a promoter metal selected from the group consisting of alkali metals, alkaline earth metals, transition metals from Group IIIB, Group IVB, Group VB, Group VIB, Group VIIB, Group VIIIB, Group IB, and Group IIB, Group IIIA elements, Group IVA elements, lanthanides, actinides, and combinations thereof. In some embodiments, additional promoter metals that can be used to prepare the promoted zeolite of the disclosed catalyst composition include, but are not limited to, copper (Cu), cobalt (Co), nickel (Ni), lanthanum (La), manganese (Mn), iron (Fe), vanadium (V), silver (Ag), cerium (Ce), neodymium (Nd), praseodymium (Pr), titanium (Ti), chromium (Cr), zinc (Zn), tin (Sn), niobium (Nb), molybdenum (Mo), hafnium (Hf), yttrium (Y), tungsten (W), and combinations thereof. In some embodiments, the promoter metal is copper or iron. For example, copper or iron can be ion-exchanged to form Cu-chabazite or Fe-chabazite. When using copper acetate, in a specific embodiment, the copper concentration of the liquid copper solution used in copper ion exchange is in the range of about 0.01 to about 0.4 mol, more specifically in the range of about 0.05 to about 0.3 mol.
[0221] Accelerator metals can be exchanged into zeolites via a liquid-phase exchange process, where soluble metal ions exchange with protons or ammonium or sodium ions located within the pores of the zeolite. This exchange can also be carried out by a solid-state method, wherein solid particles of accelerator metal oxides or metal salts are mixed with zeolite powder and treated in a specific temperature and gas environment, which may or may not contain vapor. The exchange process can also be accomplished via an in-situ process during slurry preparation, where fine metal oxide particles are suspended in the zeolite slurry under conditions suitable for solid-liquid interactions. In some embodiments, the zeolite must be subjected to NH4 oxidation before the accelerator metal is exchanged into the zeolite material disclosed herein. + Exchange and calcination, as known in the art, are used to obtain the H of the corresponding materials. + form.
[0222] To further promote the SCR of nitrogen oxides, in some embodiments, zeolites can be promoted using two or more metals (e.g., a combination of copper and one or more other metals). When the promoted zeolite material includes two or more metals, multiple metal precursors (e.g., copper and iron precursors) can undergo ion exchange simultaneously or separately. In some embodiments, a second metal can be exchanged into the zeolite material initially promoted with the first metal (e.g., the second metal can be exchanged into a copper-promoted zeolite material).
[0223] The amount of metal ions exchanged in the metal-promoted zeolite can vary. In one or more embodiments, the promoter metal content, calculated as metal oxide, ranges independently from about 0.01 wt% to about 15 wt.%, about 0.5 wt% to about 12 wt%, or about 1.0 wt% to about 10 wt% based on the total weight of the respective calcined zeolite (containing the promoter metal), and is reported on a volatile-free basis. In some embodiments, the promoter metal content, calculated as oxide, is at least about 0.1 wt% based on the total weight of the calcined zeolite (including the promoter metal), and is reported on a volatile-free basis. In a specific embodiment, the promoter metal of the zeolite comprises Cu, and the Cu content, calculated as CuO, ranges from about 0.1 wt% to about 20 wt%, including about 0.5 wt% to about 17 wt%, about 2 wt% to about 15 wt%, or about 2 wt% to about 10 wt%, in each case based on the total weight of the calcined zeolite reported on a volatile-free basis.
[0224] In some embodiments, the zeolite (including the accelerator metal) can be defined by the ratio of the accelerator metal to aluminum within the zeolite. For example, in some embodiments, the weight ratio of the accelerator metal to aluminum is in the range of about 0.002 to about 0.5. In a specific embodiment, the accelerator metal of the zeolite comprises Cu, and the atomic ratio of copper to aluminum in the zeolite is about 0.1 to about 0.5 (e.g., the Cu / Al ratio is about 0.1 to about 0.5).
[0225] The types of copper potentially present in zeolite materials (e.g., copper oxide, metallic, and ion-exchange copper) can be identified by monitoring the vibrations of perturbed TOT bonds (Si-O-Al and Si-O-Si) using diffuse reflectance Fourier transform infrared (DRIFT) spectroscopy. The use of this FTIR technique has been demonstrated in references such as Giamello et al., J. Catal. 136, 510-520 (1992). The structural vibrations of TOT bonds in zeolites, in both asymmetric and symmetric modes, are observed at 1300–1000 cm⁻¹. -1 and 850-750cm -1 An absorption peak is observed at this location. The asymmetric TOT vibrational frequency of the oxygen-containing ring is highly sensitive to its interaction with cations, and therefore, when interacting with cations, the IR band extends from the typical 1000-1300 cm⁻¹. -1 (Positional characteristics of the unperturbed ring) shifted to approximately 850-1000 cm -1The shift band appears in the transport window between two strong bands of TOT asymmetric and symmetric vibrations. The position of this shift band depends on the nature of the cation. This perturbed TOT bond vibration is observed when copper ions exchange to cation exchange sites in the zeolite framework due to the strong interaction between copper ions and adjacent oxygen atoms in the framework structure. The peak position depends on the state of the compensating cation and the structure of the zeolite framework. In some embodiments, powder samples of copper-promoted zeolites, as disclosed herein, show TOT bond peaks measured by DRIFT spectroscopy that shift to higher wavenumbers relative to copper-promoted zeolites prepared by methods in which OSDA is a single quaternary ammonium ion (e.g., N,N,N-trimethylcyclohexammonium alone or N,N,N-trimethyladamantane-1-ammonium (TMAda)).
[0226] SCR catalyst composition
[0227] This disclosure provides a selective catalytic reduction (SCR) catalyst composition that effectively catalyzes the removal of NO from engine exhaust gases (e.g., exhaust gases from lean-burn engines) in the presence of a reducing agent. x The reduction of the catalyst composition comprises a microporous zeolite as disclosed herein.
[0228] In some embodiments, the SCR catalyst composition may further comprise a binder, such as a ZrO2 binder derived from a suitable precursor like zirconium oxyacetate or any other suitable zirconium precursor like zirconium oxynitrate. The zirconium oxyacetate binder provides a uniform and intact coating after thermal aging, for example, when the catalyst is exposed to temperatures of at least about 600°C, such as about 800°C and higher, and high water vapor environments of about 5% or higher. Other potentially suitable binders include, but are not limited to, alumina and silica. Alumina binders include alumina, aluminum hydroxide, and alumina hydroxyaluminate. Colloidal forms of aluminum salts and alumina may also be used. Silica binders comprise various forms of SiO2, including silicates and colloidal silica. The binder composition may comprise any combination of zirconium oxide, alumina, and silica. Other exemplary binders include boehmite, γ-alumina, or δ / θ alumina, as well as silica sol. When present, the amount of binder is typically about 1-5 wt% of the total carrier coating loading. Alternatively, the binder can be zirconium oxide-based or silica-based, such as zirconium acetate, zirconium oxide sol, or silica sol. When present, the amount of alumina binder used is typically about 0.05 g / in. 3 Up to approximately 1g / in 3 .
[0229] Catalysts
[0230] In another aspect, an SCR article is provided that effectively catalyzes NO from engine exhaust gas (e.g., from lean-burn engine exhaust gas) in the presence of a reducing agent. x The SCR article comprises a substrate and an SCR catalyst composition as disclosed herein disposed on at least a portion thereof, the substrate having an inlet end and an outlet end defining a defined total length.
[0231] base
[0232] In one or more embodiments, the SCR catalyst composition of the present invention is arranged on a substrate to form a catalytic article. Catalytic articles comprising a substrate are typically used as part of an exhaust gas treatment system (e.g., catalyst articles, including but not limited to articles comprising the SCR composition disclosed herein). A useful substrate is three-dimensional, having a length, diameter, and volume similar to a cylinder. The shape need not conform to a cylinder. The length is the axial length defined by the inlet end and the outlet end.
[0233] According to one or more embodiments, the substrate used for the disclosed composition may be made of any material commonly used in the preparation of automotive catalysts and will typically include a metal or ceramic honeycomb structure. The substrate typically provides multiple wall surfaces on which a carrier coating composition is applied and adhered, thereby serving as the substrate for the catalyst composition.
[0234] The ceramic substrate can be made of any suitable refractory material, such as cordierite, cordierite-α-alumina, aluminum titanate, silicon titanate, silicon carbide, silicon nitride, zircon-mullite, spodumene, alumina-silica-magnesium oxide, zirconium silicate, sillimanite, magnesium silicate, zircon, selenite, α-alumina, aluminosilicates, etc.
[0235] The substrate can also be metallic, including one or more metals or metal alloys. Metallic substrates can include any metallic substrate, such as those with openings or "punch-outs" in the channel walls. Metallic substrates can take various shapes, such as granules, compressed metal fibers, corrugated sheets, or integral foam. Specific embodiments of metallic substrates include heat-resistant base metal alloys, particularly those in which iron is a basic or major component. Such alloys may contain one or more of nickel, chromium, and aluminum, and in each case, based on the weight of the substrate, the total amount of these metals may advantageously include at least about 15 wt% (by weight) of the alloy, for example, about 10 wt% to about 25 wt% of chromium, about 1 wt% to about 8 wt% of aluminum, and about 0 to about 20 wt% of nickel. Embodiments of metallic substrates include substrates with straight channels; protruding blades with axial pathways to interrupt gas flow and open communication between channels; and conduits with blades and orifices to enhance gas transport between channels, allowing radial gas transport in the bulk.
[0236] Any suitable substrate of the catalyst disclosed herein can be used, such as a monolithic substrate (“flow-through substrate”) having fine parallel gas flow channels extending through it from the inlet or outlet face of the substrate, such that the channels are open to the fluid flowing through them. Another suitable substrate belongs to the type having multiple fine, substantially parallel gas flow channels extending along the longitudinal axis of the substrate, wherein typically each channel is blocked at one end of the substrate body, while alternative channels are blocked at opposite end faces (“wall-flow filter”). Flow-through and wall-flow substrates are also taught, for example, in International Application Publication No. WO2016 / 070090, which is incorporated herein by reference in its entirety.
[0237] In some embodiments, the catalyst substrate comprises a honeycomb substrate in the form of a wall-flow filter or a flow-through substrate. In some embodiments, the substrate is a wall-flow filter. In some embodiments, the substrate is a flow-through substrate. Flow-through substrates and wall-flow filters will be discussed further below.
[0238] Flow-through substrate
[0239] In some embodiments, the substrate is a flow-through substrate (e.g., a monolithic substrate, including a flow-through honeycomb monolithic substrate). The flow-through substrate has narrow, parallel airflow channels extending from the inlet end of the substrate to the outlet end, such that the channels are open to fluid flow. These channels, from their fluid inlets to their fluid outlets, are substantially straight paths defined by walls on or therein disposed with a catalytic coating, allowing the gas flowing through the channels to contact the catalytic material. The flow channels of the flow-through substrate are thin-walled pathways, which can be of any suitable cross-sectional shape and size, such as trapezoidal, rectangular, square, sinusoidal, hexagonal, elliptical, circular, etc. As mentioned above, the flow-through substrate can be ceramic or metallic.
[0240] For example, a flow-through substrate can have approximately 50 inches. 3 Approximately 1200 inches 3 The volume, approximately 60 pores per square inch (cpsi) to approximately 500 cpsi or up to approximately 900 cpsi, such as a pore density (inlet opening) of approximately 200 to approximately 400 cpsi and a wall thickness of approximately 50 to approximately 200 micrometers or approximately 400 micrometers.
[0241] Wall flow filter substrate
[0242] In some embodiments, the substrate is a wall-flow filter, which typically has multiple thin, substantially parallel airflow channels extending along the longitudinal axis of the substrate. Typically, each channel is blocked at one end of the substrate body, with alternating channels blocked at opposite end faces. Such a monolithic wall-flow filter substrate can contain up to about 900 or more flow channels (or “pores”) per square inch of cross-section, but much fewer can be used. For example, the substrate can have about 7 to 600 pores per square inch, more typically about 100 to 400 pores per square inch (“cpsi”). The cross-section of the pores can be rectangular, square, circular, elliptical, triangular, hexagonal, or other polygonal shapes. As mentioned above, the wall-flow filter substrate can be ceramic or metallic.
[0243] refer to Figure 1 An exemplary wall-flow filter substrate has a cylindrical shape and a cylindrical outer surface having a diameter D and an axial length L. Figure 2 A cross-sectional view of the substrate portion of the integral wall-flow filter is shown, illustrating alternating blocked and open channels (bubbles). Blocked or plugged ends 100 alternate with open channels 101, each opposite end being open and closed respectively. The filter has an inlet end 102 and an outlet end 103. Arrows passing through porous bubble walls 104 indicate that exhaust gas flows into the open bubble end, diffuses through the porous bubble wall 104, and exits at the open outlet bubble end. Blocked ends 100 impede gas flow and promote diffusion through the bubble walls. Each bubble wall has an inlet side 104a and an outlet side 104b. The channels are surrounded by the bubble walls.
[0244] The volume of the substrate for a wall-flow filter product can be, for example, about 50 cm³. 3 Approximately 100 inches 3 Approximately 200 inches 3 Approximately 300 inches 3 Approximately 400 inches 3 Approximately 500 inches 3 Approximately 600 inches 3 Approximately 700 inches 3 Approximately 800 inches 3 Approximately 900 inches 3 or about 1000 inches 3 approximately 1500in 3 Approximately 2000 inches 3 Approximately 2500 inches 3 Approximately 3000 inches 3 Approximately 3500 inches 3 Approximately 4000 inches 3 Approximately 4500 inches 3 or about 5000 inches 3The wall thickness of the substrate for wall-flow filters is typically from about 50 micrometers to about 2000 micrometers, for example, from about 50 micrometers to about 450 micrometers or from about 150 micrometers to about 400 micrometers.
[0245] The walls of wall-flow filters are porous and typically have a wall porosity of at least about 40% or at least about 50%, with an average pore size of at least about 10 micrometers before the application of the functional coating. For example, in some embodiments, the wall-flow filter article substrate will have a porosity of ≥40%, ≥50%, ≥60%, ≥65%, or ≥70%. For example, before the application of the catalytic coating, the wall-flow filter article substrate will have a wall porosity of about 50%, about 60%, about 65%, or about 70% to about 75%, and an average pore size of about 10 or about 20 to about 30 or about 40 micrometers. The terms “wall porosity” and “substrate porosity” refer to the same thing and are interchangeable. Porosity is the ratio of empty volume (or pore volume) to the total volume of the substrate material. Pore size and pore size distribution are typically determined by Hg porosimetry.
[0246] Substrate coating process
[0247] To prepare the SCR catalyst article of this disclosure, a substrate described herein is coated with the SCR catalyst composition disclosed herein. The coating is a "catalytic coating composition" or "catalytic coating". "Catalyst composition" and "catalytic coating composition" are synonyms.
[0248] Typically, a catalyst composition is prepared as described herein and coated onto a substrate. This method may involve mixing a catalyst composition (or one or more components of a catalyst composition) generally disclosed herein with a solvent (e.g., water) to form a slurry for coating the catalyst substrate. In addition to the catalyst composition, the slurry may optionally contain a variety of additional components. Typical additional components include, but are not limited to, binders as described above, and additives for controlling, for example, the pH and viscosity of the slurry. Additional components may include hydrocarbon (HC) storage components (e.g., zeolites), associative thickeners, and / or surfactants (including anionic, cationic, nonionic, or amphoteric surfactants). The typical pH range of the slurry is from about 3 to about 6. Acidic or basic substances may be added to the slurry to adjust the pH accordingly. For example, in some embodiments, the pH of the slurry is adjusted by adding aqueous acetic acid.
[0249] The slurry can be ground to a smaller particle size, enhancing particle mixing and the formation of homogeneous materials. Grinding can be performed in a ball mill, continuous mill, or other similar equipment, and the solids content of the slurry can be, for example, about 20-60 wt.%, more specifically about 20-40 wt.%. In one embodiment, the ground slurry is characterized by D 90The particle size is about 1 to about 40 micrometers, preferably about 2 to about 20 micrometers, and more preferably about 4 to about 15 micrometers.
[0250] The catalyst compositions of the present invention can generally be applied in the form of one or more support coatings containing the SCR catalyst compositions disclosed herein. The support coating is formed by preparing a slurry containing a specific solids content (e.g., about 10% to about 60% by weight) of the catalyst composition (or one or more components of the catalyst composition) in a liquid support, then applying it to a substrate using any support coating technique known in the art, and drying and calcining to provide a coating. If multiple coatings are applied, the substrate is dried and / or calcined after the application of each support coating and / or after the application of the desired number of multiple support coatings. In one or more embodiments, the catalytic material is applied to the substrate as a support coating.
[0251] After calcination, the catalyst loading obtained by the above-described carrier coating technology can be determined by calculating the difference in weight between the coated and uncoated substrates. It will be apparent to those skilled in the art that the catalyst loading can be altered by changing the rheological properties of the slurry. Furthermore, the coating / drying / calcination process for generating the carrier coating layer (coating) can be repeated as needed to configure the coating to the desired loading level or thickness, meaning that more than one carrier coating can be applied.
[0252] Coating configuration
[0253] The catalytic coating of the present invention may comprise one or more coatings, wherein at least one layer comprises the catalyst composition of the present invention or one or more components of the catalyst composition. The catalytic coating may include one or more thin adhesive coatings disposed on and adhered to at least a portion of a substrate. The entire coating comprises a single “coating”.
[0254] In some embodiments, the catalytic article of the present invention may include the use of one or more catalyst layers and combinations thereof. The catalytic material may be present only on the inlet side of the substrate wall, only on the outlet side, on both the inlet and outlet sides, or the wall itself may be wholly or partially composed of the catalytic material. The catalytic coating may be on the surface of the substrate wall and / or in the pores of the substrate wall, i.e., “in the substrate wall” and / or “on the substrate wall”. Therefore, the phrase “carrier coating disposed on a substrate” refers to any surface, such as on the wall surface and / or on the pore surface.
[0255] A carrier coating can be applied so that different coatings can be in direct contact with the substrate. Alternatively, one or more "undercoating layers" can be present such that at least a portion of the catalytic coating or multiple coatings is not in direct contact with the substrate (but is in contact with the undercoating layer). One or more "outer coating layers" can also be present such that at least a portion of the one or more coatings is not directly exposed to the airflow or atmosphere (but is in contact with the outer coating layer).
[0256] Alternatively, the catalyst composition of the present invention may be in a top coating above a bottom coating. The catalyst composition may be present in both the top and bottom layers. Either layer may extend the entire axial length of the substrate; for example, the bottom layer may extend the entire axial length of the substrate, and the top layer may extend the entire axial length of the substrate over the bottom layer. Each of the top and bottom layers may extend from either an inlet or an outlet end.
[0257] For example, both the bottom coating and the top coating may extend from the same substrate end, wherein the top coating partially or completely covers the bottom coating, and wherein the bottom coating extends part or all of the length of the substrate, and wherein the top coating extends part or all of the length of the substrate. Alternatively, the top coating may cover a portion of the bottom coating. For example, the bottom coating may extend the entire length of the substrate, and the top coating may extend from the inlet or outlet end for approximately 10%, approximately 20%, approximately 30%, approximately 40%, approximately 50%, approximately 60%, approximately 70%, approximately 80%, or approximately 90% of the substrate length.
[0258] Alternatively, the bottom layer may extend from the inlet or outlet end for about 10%, about 15%, about 25%, about 30%, about 40%, about 45%, about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, about 85%, or about 95% of the base length, and the top layer may extend from the inlet or outlet end for about 10%, about 15%, about 25%, about 30%, about 40%, about 45%, about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, about 85%, or about 95% of the base length, wherein at least a portion of the top layer covers the bottom layer. This "covered" area may, for example, extend from about 5% to about 80% of the base length, such as about 5%, about 10%, about 20%, about 30%, about 40%, about 50%, about 60%, or about 70% of the base length.
[0259] In some embodiments, the oxidation catalyst composition disclosed herein disposed on a substrate as disclosed herein comprises a first carrier coating disposed over at least a portion of the length of the catalyst substrate.
[0260] In some embodiments, a first support coating is disposed directly on the catalyst substrate, and a second support coating (which may be the same as or contain different catalysts or catalyst components) is disposed on at least a portion of the first support coating. In some embodiments, the second support coating is disposed directly on the catalyst substrate, and the first support coating is disposed on at least a portion of the second support coating. In some embodiments, the first support coating is disposed directly on the catalyst substrate from the inlet end to a length of about 10% to about 50% of the total length; and the second support coating is disposed on at least a portion of the first support coating. In some embodiments, the second support coating is disposed directly on the catalyst substrate from the inlet end to a length of about 50% to about 100% of the total length; and the first support coating is disposed on at least a portion of the second support coating. In some embodiments, the first support coating is disposed directly on the catalyst substrate from the inlet end to a length of about 20% to about 40% of the total length, and the second support coating extends from the inlet end to the outlet end. In some embodiments, the first support coating is disposed directly on the catalyst substrate from the outlet end to a length of about 10% to about 50% of the total length, and the second support coating is disposed on at least a portion of the first support coating. In some embodiments, a first carrier coating is disposed directly on the catalyst substrate from the outlet end to a length of about 20 to about 40% of the total length, and a second carrier coating extends from the inlet end to the outlet end. In some embodiments, a second carrier coating is disposed directly on the catalyst substrate from the outlet end to a length of about 50% to about 100% of the total length, and the first carrier coating is disposed on at least a portion of the second carrier coating. In some embodiments, a first carrier coating is disposed directly on the catalyst substrate, covering 100% of the total length, and a second carrier coating is disposed on top of the first carrier coating, covering 100% of the total length. In some embodiments, a second carrier coating is disposed directly on the catalyst substrate, covering 100% of the total length, and a first carrier coating is disposed on top of the second carrier coating, covering 100% of the total length.
[0261] The catalytic coating can advantageously be “partitioned,” comprising partitioned catalytic layers, i.e., wherein the axial length of the catalytic coating across the substrate comprises a varying composition. This can also be referred to as “lateral partitioning.” For example, layers may extend from the inlet end to the outlet end, extending approximately 10%, approximately 20%, approximately 30%, approximately 40%, approximately 50%, approximately 60%, approximately 70%, approximately 80%, or approximately 90% of the substrate length. Another layer may extend from the outlet end to the inlet end, extending approximately 10%, approximately 20%, approximately 30%, approximately 40%, approximately 50%, approximately 60%, approximately 70%, approximately 80%, or approximately 90% of the substrate length. Different coatings may be adjacent to each other and not overlap. Alternatively, different layers may partially overlap each other, thereby providing a third “intermediate” zone. The intermediate zone may extend from approximately 5% to approximately 80% of the base length, for example, approximately 5%, approximately 10%, approximately 20%, approximately 30%, approximately 40%, approximately 50%, approximately 60%, or approximately 70% of the base length.
[0262] The regions disclosed herein are defined by the relationship between the coatings. For different coatings, there are many possible partitioning configurations. For example, there can be upstream and downstream regions, upstream, intermediate, and downstream regions, or four distinct regions, etc. When two layers are adjacent and do not overlap, there are upstream and downstream regions. When two layers overlap to some extent, there are upstream, downstream, and intermediate regions. For example, when the coating extends the entire length of the substrate and different coatings extend a certain length from the exit end and cover a portion of the first coating, upstream and downstream regions exist.
[0263] For example, an SCR catalyst may include an upstream region comprising a first support coating layer and a downstream region comprising a second support coating layer containing different catalyst materials or components. Alternatively, the upstream region may comprise the second support coating layer, and the downstream region may comprise the first support coating layer.
[0264] In some embodiments, a first carrier coating is disposed on the catalyst substrate from the inlet end to a length of about 10% to about 50% of the total length; and a second carrier coating is disposed on the catalyst substrate from the outlet end to a length of about 50% to about 90% of the total length.
[0265] Figures 3a, 3b, and 3c show some possible coating configurations with two coatings. A substrate wall 200 is shown, on which coatings 201 (top coating) and 202 (bottom coating) are arranged. This is a simplified illustration; in the case of a porous wall-flow substrate, the pores and coatings adhered to the pore walls are not shown, nor are the clogging ends. In Figure 3a, coatings 201 and 202 each extend the entire length of the substrate, with the top layer 201 covering the bottom layer 202. The substrate in Figure 3a does not contain a partitioned coating configuration. Figure 3b shows a partitioned configuration with coatings 202 and 201, where coating 202 extends approximately 50% of the substrate length from the outlet to form a downstream zone 204, and coating 201 extends approximately 50% of the substrate length from the inlet to provide an upstream zone 203. In Figure 3c, the bottom coating 202 extends approximately 50% of the substrate length from the outlet, and the top coating 201 extends more than 50% of its length from the inlet and covers a portion of layer 202, providing an upstream zone 203, an intermediate cover zone 205, and a downstream zone 204. Figures 3a, 3b, and 3c can be used for SCR catalyst compositions on illustrated wall-flow or flow-through substrates.
[0266] In some embodiments, the substrate is a honeycomb substrate. In some embodiments, the honeycomb substrate is a flow-through substrate or a wall-flow filter. In some embodiments, the SCR catalyst composition disclosed herein, when incorporated into an SCR catalyst article disclosed herein, effectively catalyzes NO from engine exhaust gas (e.g., exhaust gas from a lean-burn engine) in the presence of a reducing agent. x The reduction. In some embodiments, the SCR article is characterized by its SCR activity at various temperatures. In some embodiments, NO x Effective reduction of NO is carried out at a temperature above about 150°C and below about 700°C. In some embodiments, NO... x Effective reduction is carried out at temperatures ranging from approximately 200°C to approximately 600°C.
[0267] Exhaust gas treatment system
[0268] In another aspect, a system for treating exhaust gas from an engine is provided, comprising an SCR article as disclosed herein, positioned downstream and in fluid communication with an engine (e.g., a lean-burn engine) that generates the exhaust gas flow. The engine may be, for example, a diesel engine, operating under combustion conditions where air exceeds the air required for stoichiometric combustion, i.e., lean conditions. In other embodiments, the engine may be a gasoline engine (e.g., a lean-burn gasoline engine) or an engine associated with a stationary source (e.g., a generator or pumping station). The exhaust gas treatment system typically contains more than one catalytic article located downstream of the engine and in fluid communication with the exhaust gas flow. The system may contain, for example, a selective catalytic reduction catalyst (SCR), a diesel oxidation catalyst (DOC), and one or more articles containing a reducing agent injector, a soot filter, an ammonia oxidation catalyst (AMOx), or a lean NOx trap (LNT). The article containing the reducing agent injector is a reducing article. The reduction system includes a reducing agent injector and / or a pump and / or a reservoir, etc. The treatment system of the present invention may further include a soot filter and / or an ammonia oxidation catalyst. The soot filter can be non-catalyzed or catalyzed (CSF). For example, from upstream to downstream, the treatment system of the present invention may include articles containing DOC, CSF, urea injectors, SCR products, and articles containing AMOx. It may also include a dilute NOx trapping agent (LNT).
[0269] The relative positions of the various catalytic components present within the exhaust gas treatment system can vary. In the exhaust gas treatment system and method of the present invention, the exhaust gas stream is contained into the product or treatment system by entering at an upstream end and exiting at a downstream end. The inlet end of the substrate or product is synonymous with the "upstream" end or "front" end. The outlet end is synonymous with the "downstream" end or "rear" end. The treatment system is typically located downstream of the internal combustion engine and is in fluid communication with the internal combustion engine.
[0270] Figure 4 An exemplary emissions treatment system is illustrated, depicting a schematic diagram of exhaust treatment system 20. As shown, the exhaust treatment system may include multiple catalyst components connected in series downstream of engine 22 (such as a lean-burn engine). At least one of the catalyst components will be the SCR catalyst of the present invention as set forth herein. The catalyst composition of the present invention can be combined with many additional catalyst materials and can be placed in various locations compared to additional catalyst materials. Figure 4 Five catalyst components 24, 26, 28, 30, and 32 are shown in series; however, the total number of catalyst components can vary, and the five components are merely one example.
[0271] Non-limiting, Table 3 shows various exhaust gas treatment system configurations for one or more embodiments. Note that each catalyst is connected to the next catalyst via an exhaust pipe, such that the engine is upstream of catalyst A, catalyst A is upstream of catalyst B, catalyst B is upstream of catalyst C, catalyst C is upstream of catalyst D, and catalyst D is upstream of catalyst E (if present). References to component AE in the table may be related to... Figure 4 Cross-referencing of the same name in the same file.
[0272] The LNT catalysts listed in Table 3 can be those traditionally used for NO production. x Any catalyst that acts as a trap, and typically contains NO. x The adsorbent composition comprises base metal oxides (BaO, MgO, CeO2, etc.) and platinum group metals (e.g., Pt and Rh) for catalyzing the oxidation and reduction of NO.
[0273] The LT-NA catalysts listed in Table 3 can adsorb NO at low temperatures (<250℃). x (e.g., NO or NO2) and any catalyst that releases it into the gas stream at high temperatures (>250°C). The released NO x Typically, N2 and H2O are converted via downstream SCR or SCRoF catalysts. LT-NA catalysts usually contain Pd-promoted zeolites or Pd-promoted refractory metal oxides.
[0274] References to SCR in the table refer to SCR catalysts, which may include the SCR catalyst compositions of the present invention. References to SCRofF (or SCR on a filter) refer to particulate or soot filters (e.g., wall-flow filters), which may include the SCR catalyst compositions of the present invention. In the presence of both SCR and SCRofF, one or both may include the SCR catalyst of the present invention, or one of the catalysts may include a conventional SCR catalyst (e.g., an SCR catalyst with a conventional metal loading level).
[0275] The reference to AMOx in the table refers to an ammonia oxidation catalyst, which may be placed downstream of the catalyst of one or more embodiments of the present invention to remove any slipping ammonia from the exhaust gas treatment system. In certain embodiments, the AMOx catalyst may include a PGM component. In one or more embodiments, the AMOx catalyst may include a base coating having a PGM and a top coating having SCR functionality.
[0276] As those skilled in the art will recognize, in the configurations listed in Table 3, any one or more components A, B, C, D, or E can be arranged on a particulate filter such as a wall-flow filter, or on a flow-through honeycomb substrate. In one or more embodiments, the engine exhaust system comprises one or more catalyst compositions mounted in a location near the engine (in a close-fitting location, CC), while additional catalyst compositions are located below the carrier (in a floor-mounted location, UF). In one or more embodiments, the exhaust treatment system may further include a urea injection component.
[0277] Table 3. Possible exhaust gas treatment system configurations
[0278] DOC SCR Optional AMOx - - DOC SCRoF Optional AMOx - - DOC SCRoF SCR Optional AMOx - DOC SCR SCRoF Optional AMOx - DOC CSF SCR Optional AMOx - LNT CSF SCR Optional AMOx - LNT SCRoF SCR Optional AMOx -
[0279] Methods for treating engine exhaust
[0280] Another aspect of the invention relates to a method for treating exhaust gas from an engine, such as a lean-burn engine, particularly a lean-burn gasoline engine or diesel engine. The method may include placing an SCR catalyst article according to one or more embodiments of the invention downstream of the engine and allowing the engine exhaust gas to flow through the catalyst. In one or more embodiments, the method further includes placing additional catalyst components downstream of the engine as described above. This catalyst composition, article, system, and method are suitable for treating exhaust gas from internal combustion engines, such as gasoline, light-duty diesel, and heavy-duty diesel engines. The catalyst composition is also suitable for treating emissions from stationary industrial processes, removing harmful or toxic substances from indoor air, or for catalysis in chemical reaction processes.
[0281] The articles, systems, and methods of the present invention are suitable for treating exhaust gas streams from mobile emission sources such as trucks and automobiles. The articles, systems, and methods of the present invention are also suitable for treating exhaust gas streams from stationary sources such as power plants.
[0282] It will be apparent to those skilled in the art that suitable modifications and adaptations can be made to the compositions, methods, and applications described herein without departing from the scope of any implementation or aspect thereof. The compositions and methods provided are exemplary and are not intended to limit the scope of the claimed implementations. All the various implementations, aspects, and options disclosed herein can be combined in all variations. The scope of the compositions, formulations, methods, and processes described herein includes all actual or potential combinations of the implementations, aspects, options, examples, and preferences herein. All patents and publications referenced herein are incorporated herein by reference for their specific teachings as mentioned, unless otherwise specifically stated by inclusion.
[0283] The present invention will now be described with reference to the following embodiments. Before describing several exemplary embodiments of the invention, it should be understood that the invention is not limited to the details of the construction or process steps set forth in the following description. The invention can have other embodiments and can be practiced or implemented in various ways.
[0284] experiment
[0285] General Program
[0286] The surface areas of mesoporous (or matrix) and zeolite (microporous) samples were determined according to ISO 9277 using the N2 adsorption porosity determination method on a Micromeritics TriStar 3000 series instrument. Samples were degassed on a Micromeritics SmartPrep degasser for a total of 6 hours (2 hours ramped to 300°C, then held at 300°C for 4 hours under a stream of dry nitrogen). The nitrogen BET surface area was determined using five partial pressure points between 0.05 and 0.20. The same five partial pressure points were used for determination, and the surface areas of zeolite and matrix were calculated using Harkins and Jura t-plots. Samples with diameters greater than [a certain value] were considered [to be included in the determination]. The pores contribute to the surface area of the matrix.
[0287] Diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) measurements were performed on a Thermo Nicolet FTIR instrument in a Harrick environmental chamber equipped with an MCT detector and a ZnSe window. The sample was ground into a fine powder using a mortar and pestle and then placed in sample cups. The sample powder was first dehydrated in flowing Ar at a flow rate of 40 ml / min at 400 °C for 1 hour, and then cooled to 30 °C. The sample was then subjected to spectral analysis, with KBr used as a reference.
[0288] Preparation of small-pore zeolite materials
[0289] In all cases, the same Si and Al sources were used in gel preparation, and crystallization was carried out under autogenous pressure in a 2L stirred autoclave. The product was separated by filtration, dried, and calcined (540°C, 6 hours) to obtain the product (analyzed by XRD), subjected to single or multiple NH4 reactions. + Exchange until the Na₂O content reaches <500 ppm. Table 4 lists the gel compositions of the zeolite materials leading to the comparison (Examples 1-3) and the invention (Examples 4-6) and their corresponding products SAR. All materials were synthesized at 170°C with crystallization times of 30-72 hours.
[0290] Examples 1-3 (Comparison)
[0291] For each synthesis, trimethyladamantyl ammonium hydroxide (TMadaOH) was the only OSDA used. As shown in Table 4, the gel composition (Si / Al ratio, OH / Si ratio, H2O to Si ratio) differed for each example. For Example 3, no Na was added to the gel. + All crystallization produced products with a CHA phase crystallinity >90% and a correspondingly high microporous surface area (>500 μm²). 2 / g). The material from Example 2 was calcined and used as seed crystals in Examples 4-7 (the use of CHA seed crystals in the synthetic gel is optional).
[0292] Example 4 (Comparison)
[0293] Comparative Example 4 illustrates another sodium-free synthesis method, in which the gel and product SAR differ from those of the embodiments of the invention. For this synthesis, trimethylcyclohexylammonium hydroxide (TMChAOH) was used as the OSDA. No Na was added to the gel. + Although some Na present in the seed zeolite was added for crystallization, this explains the presence of Na in the product. Tetramethylammonium hydroxide (TMAOH) was added at a ratio of 0.09 relative to Si; since tetramethylammonium was not found in the product, it is inferred that it did not serve as a template for CHA zeolite formation. Crystallization produced a zeolite with a CHA phase crystallinity >90% and a correspondingly high microporous surface area (>500 μm). 2 / g).
[0294] Examples 5-7 (Invention)
[0295] For each synthesis, hexamethylammonium dihydride (HMOH) or octamethylammonium dihydride (OMOH) was used as the first OSDA source, and TMAdaOH was used as the second OSDA source. For Examples 5 and 7, Na was not used. + Adding Na to the gel, although some Na present in the seed zeolite was added for crystallization, explains the presence of Na in the product. For example, 6, Na... + Added to the synthetic gel. Not wanting to be bound by theory, the different Na / Al ratios observed in the product zeolites could indicate different aluminum distributions in these zeolite materials relative to Comparative Examples 1-4. Crystallization produced zeolites with a CHA phase crystallinity >90%, and correspondingly high microporous surface areas (>500 m²). 2 / g).
[0296] Table 4. Synthetic gel composition
[0297]
[0298]
[0299] Without being bound by theory, it is believed that the introduction of bis-quaternary ammonium compounds (HMOH or OMOH), which have significantly different structures from the mono-quaternary TMAdaOH typically used alone to synthesize CHA zeolite, indicates a different distribution of Al in the product zeolite, compared to CHA zeolite synthesized solely with TMAdaOH or with a mixture of two mono-quaternary ammonium compounds.
[0300] To further evaluate the incorporation degree of each OSDA in the zeolite products, elemental analysis was performed on the washed original products from Examples 4, 5, and 6 of this invention. The C / N molar ratios of TMAdaOH, HMOH, and OMOH were 13, 6, and 7, respectively. The elemental analysis results of Examples 4, 5, and 6 showed that the C / N molar ratios of the products were 10.1, 11, and 11.4, respectively, indicating that for all materials of this invention, there was significant incorporation of both mono- and di-quaternary ammonium OSDA in the final products before calcination.
[0301] Furthermore, as demonstrated by the increased C / N ratio in Example 4 compared to Example 5, the Na used... + The concentration of Na can help control the degree of incorporation of the bisquaternary ammonium salt OSDA in the CHA product (and therefore, the Al distribution). Specifically, an increase in the C / N ratio indicates the addition of Na to the synthetic gel used in Example 5 of the invention. + This reduces the incorporation of bisquaternary ammonium OSDA (HMOH) into the CHA zeolite product of Example 5 of the present invention.
[0302] Example 8. Copper-exchanged CHA zeolite material
[0303] Materials from Examples 1, 4, and 5 (all NH4) + (Form) calcined at 450℃ for 6 hours to obtain H + CHA zeolite in form. Each sample was evaluated by Cu exchange isotherm experiments and FTIR measurements of the copper-exchanged samples. Cu exchange was performed at 60°C using aqueous solutions of copper acetate at different concentrations. Comparison of the isotherms of Examples 1 and 4 shows that the material of Example 5 ( Figure 5 Significantly different similar slopes. In 0.1 M Cu +2 The absorption at certain concentrations (measured as wt% of copper in the form of CuO) follows the expected trend (i.e., materials with higher Al content (lower SAR) show higher copper absorption). However, at higher Cu concentrations... 2+ Below (e.g., equal to or higher than 0.2 M), Example 5 of the present invention shows a significantly higher Cu absorption than expected based on product SAR. This is in contrast to using only TMAda + Or TMChA +The difference in balanced Cu absorption compared to the synthesized CHA zeolite is evidence of altered Al sites and pairing in the zeolite product. Since the density and distribution of catalytically active Cu sites in zeolite depend on the sites and proximity of aluminum atoms in the zeolite framework, this increased Cu absorption indicates the presence of a higher concentration of tightly located, negatively charged aluminum, which effectively balances the positive charge of the copper.
[0304] DRIFTS measurements of TOT bond vibrations in this material after Cu exchange ( Figure 6 This provides further evidence for the alteration of the A1 site and pairing in Example 5. Typically, at ~950 cm⁻¹ -1 The peak at that location was associated with [CuOH] at a single Al site. + The TOT bond vibrations assigned to the disturbance. For Example 5, the peak shifts to a higher wavenumber (960 cm⁻¹). -1 This indicates that the environment of [CuOH]+ substances in this material is relative to that of comparative zeolite materials (e.g., using only TMAda). + Or TMChA + Those prepared as OSDA).
Claims
1. A method for synthesizing small-pore zeolites with a CHA crystal framework structure, the method comprising: A mixture of water, aluminum source, silicon source, first organic structure directing agent source and second organic structure directing agent source is prepared to form a synthetic gel; as well as The synthetic gel is subjected to a crystallization process to crystallize the microporous zeolite; The first organic structure directing agent comprises a bis-quaternary ammonium cation, a derivative of a bis-quaternary ammonium cation, or a combination thereof, and the second organic structure directing agent comprises a mono-quaternary ammonium cation, a derivative of a mono-quaternary ammonium cation, or a combination thereof.
2. The method according to claim 1, wherein, The porous zeolite has a cage-like structure, and the diameter of the spheres that are most likely to be included in the cage-like structure is from 4.4 Å to 15 Å.
3. The method according to claim 1, wherein, The bisquaternary ammonium cation contains 8 to 20 carbon atoms.
4. The method according to claim 1, wherein, The C / N ratio of the pore zeolite is in the range of 7 to 15.
5. The method according to claim 1, wherein, Each nitrogen atom of the bisquaternary ammonium cation carries four substituents, wherein each substituent is independently selected from the group consisting of alkyl, alkenyl, aryl, aralkyl, and combinations thereof.
6. The method according to claim 1, wherein, The bisquaternary ammonium cation has a structure represented by formula I: (I) in: Substituents R1, R2, and R3 are each methyl or ethyl; or optionally, two R3 groups are linked to form -(CH2). n -bridge, where n is an integer from 1 to 3; and X is selected from the group consisting of: alkyl, cycloalkyl, alkenyl, aryl, aralkyl and combinations thereof.
7. The method according to claim 1, wherein, The bisquaternary ammonium cation is selected from the group consisting of: N1,N1,N1,N3,N3,N3-hexaethylpropane-1,3-diammonium, N1,N1,N1,N4,N4,N4-hexamethylbutane-1,4-diammonium, N1,N1,N1,N4,N4,N4-hexaethylbutane-1,4-diammonium, (E)-N1,N1,N1,N4,N4,N4-hexamethylbut-2-ene-1,4-diammonium, N1,N1,N1,N5,N5,N5-hexamethylpentane-1,5-diammonium, (E)-N1 ,N1,N1,N5,N5,N5-Hexamethylpent-2-ene-1,5-diammonium,N1,N1,N1,N6,N6,N6-Hexamethylhexane-1,6-diammonium,(E)-N1,N1,N1,N6,N6,N6-Hexamethylhexane-2-ene-1,6-diammonium,(2E,4E)-N1,N1,N1,N6,N6,N6-Hexamethylhexane-2,4-diene-1,6-diammonium,N1,N1,N1,N7,N7,N7-Hexamethylheptane-1,7-diammonium,N1,N1,N1,N 8,N8,N8-Hexamethyloctane-1,8-diammonium, N1,N1,N1,N3,N3,N3-Hexamethylcyclohexane-1,3-diammonium, N1,N1,N1,N3,N3,N3-Hexamethylbicyclo[2.2.1]heptane-1,3-diammonium, N1,N1,N1,N3,N3,N3-Hexamethylbenzene-1,3-diammonium, N1,N1,N1,N4,N4,N4-Hexamethylcyclohexane-1,4-diammonium, N1,N1,N1,N4,N4,N4-Hexamethylbicyclo[2.2.1]heptane -1,4-diammonium, N1,N1,N1,N4,N4,N4-hexamethylbicyclo[2.2.2]octane-1,4-diammonium, N1,N1,N1,N4,N4,N4-hexamethylbenzene-1,4-diammonium, 1,1,4,4-tetramethylpiperazine-1,4-dionium, 1,1,3,3-tetramethylhexahydropyrimidine-1,3-dionium, 1,1'-(1,3-phenylene)bis(N,N,N-trimethylmethaneammonium), 1,1'-(1,4-phenylene)bis(N,N,N-trimethylmethaneammonium), or combinations thereof.
8. The method according to claim 1, wherein, The first organic structure directing agent source is a bis-quaternary ammonium compound, which contains a bis-quaternary ammonium cation and an OH-selected compound. - Cl - and Br - The group consists of balanced anions.
9. The method according to claim 1, wherein, The first organic structure directing agent source includes hexamethylammonium or octamethylammonium cations.
10. The method according to any one of claims 1-9, wherein, The monoquaternary ammonium cation contains 4 to 14 carbon atoms.
11. The method according to any one of claims 1-9, wherein, The nitrogen atom of the monoquaternary ammonium cation has four substituents, each of which is independently selected from the group consisting of alkyl, alkenyl, aryl, aralkyl, and combinations thereof.
12. The method according to any one of claims 1-9, wherein, The monoquaternary ammonium cation has a structure represented by Formula II: (II) in: R1, R2, and R3 are each methyl or ethyl; and R4 is selected from the group consisting of: methyl, ethyl, hydroxyethyl, cyclohexyl, aziridine, heptyl, adamantyl, and phenyl; Alternatively, R3 and R4 together, or R2, R3 and R4 together, can be linked to form a monocyclic or bicyclic system, which can optionally be substituted by one or more methyl or OH groups.
13. The method according to any one of claims 1 to 9, wherein, The monoquaternary ammonium cation is selected from the group consisting of: tetraethylammonium, 2-hydroxy-N,N,N-trimethylethane-1-ammonium, N,N,N-trimethylcyclohexaneammonium, N,N,N-trimethyladamantane-1-ammonium (TMAda), N,N,N-trimethylbicyclo[2.2.1]heptane-2-ammonium, N,N,N-trimethylphenylammonium, 1,1-dimethylpiperidine-1-onium, 1,1,3,5-tetramethylpiperidine-1-onium, 1-methylquinine-1-onium, 3-hydroxy-1-methylquinine-1-onium, or combinations thereof.
14. The method according to any one of claims 1 to 9, wherein, The second organic structure-directing agent source is a monoquaternary ammonium compound, which contains a monoquaternary ammonium cation and an OH- cation. - Cl - and Br - The group consists of balanced anions.
15. The method according to any one of claims 1 to 9, wherein, The second organic structure directing agent source contains N,N,N-trimethyladamantane-1-ammonium cation.
16. The method according to claim 15, wherein, The first organic structure directing agent source is hexamethylammonium dihydrogen hydride (HMOH) or octamethylammonium dihydrogen hydride (OMOH), and the second organic structure directing agent source is N,N,N-trimethyladamantane-1-ammonium hydroxide (TMAdaOH).
17. The method according to any one of claims 1 to 9, wherein, The molar ratio of the first organic structure directing agent to the second organic structure directing agent is in the range of 0.001 to 1000.
18. The method according to claim 17, wherein, The molar ratio of the first organic structure directing agent to the second organic structure directing agent is from 0.1 to 10.
19. The method according to claim 18, wherein, The molar ratio of the first organic structure directing agent to the second organic structure directing agent is from 0.5 to 2.
20. The method according to any one of claims 1 to 9, wherein, The mixture also contains an inorganic structure directing agent, wherein the inorganic structure directing agent is an alkali metal cation or an alkaline earth metal cation.
21. The method according to claim 20, wherein, The alkali metal cation is selected from the group consisting of lithium, sodium, potassium, or cesium.
22. The method according to any one of claims 1 to 9, wherein, The aluminum source includes one or more of aluminum salts, aluminum metal, alumina, aluminosilicates, or zeolites.
23. The method according to claim 22, wherein, The aluminum source includes zeolites with a crystalline framework of FAU, LTA, LTL, MFI, or BEA.
24. The method according to claim 22, wherein, The aluminum source is Na. + Zeolite Y in form.
25. The method according to any one of claims 1 to 9, wherein, The silicon source is colloidal silicon dioxide, silanol compounds, alkali metal silicates, pyrolytic silicon dioxide, amorphous silicon dioxide, or aluminosilicates.
26. The method of claim 25, wherein, The silicon source is sodium silicate.
27. The method according to any one of claims 1 to 9, wherein, The OH / Si ratio of the synthesized gel is from 0.03 to 1.
0.
28. The method according to any one of claims 1 to 9, wherein, The crystallization process involves maintaining the synthesized gel at a temperature between 90°C and 250°C.
29. The method according to claim 28, wherein, The crystallization process involves maintaining the synthesized gel at a temperature of 120°C to 200°C.
30. The method according to any one of claims 1 to 9, further comprising filtering the crystals formed during the heating step.
31. The method according to any one of claims 1 to 9, further comprising calcining the zeolite at a temperature of 450°C to 750°C.
32. The method according to any one of claims 1 to 9 and 16, wherein, The microporous zeolite has a silica-alumina ratio of 6 to 100.
33. The method according to claim 32, wherein, The pore zeolite has a silica-alumina ratio of 10 to 30.
34. The method according to claim 33, wherein, The pore zeolite has a silica-alumina ratio in the range of 20 to 30.
35. The method according to any one of claims 1 to 9, wherein, The microporous zeolite has a micropore size of less than 75 μm. 2 / g MSA; and at least 450 m 2 / g of ZSA.
36. The method according to any one of claims 1 to 9, wherein, Compared to microporous zeolites synthesized using only mono-seasonal OSDA, these microporous zeolites exhibit a controlled aluminum distribution, comprising altered aluminum sites and pairing arrangements, characterized by Cu... 2+ Changes in equilibrium Cu at concentrations greater than 0.25 M 2+ absorb.
37. The method according to any one of claims 1 to 9, wherein, Before calcination, at least a portion of the pores of the microporous zeolite are occupied by the bis-quaternary ammonium cations, and at least a portion of the pores are occupied by the mono-quaternary ammonium cations.
38. The method according to claim 37, wherein, 1% to 99% of the pores are occupied by the bis-quaternary ammonium cation, and 99% to 1% of the pores are occupied by the mono-quaternary ammonium cation.
39. The method according to claim 37, wherein, 60% to 40% of the pores are occupied by the bis-quaternary ammonium cations, and 40% to 60% of the pores are occupied by the mono-quaternary ammonium cations.
40. A small-pore zeolite prepared by any one of claims 1-39.
41. A microporous zeolite with a controlled aluminum distribution, which, compared to microporous zeolites synthesized using only mono-quaternary OSDA, comprises an arrangement of anionic framework Al centers, including altered aluminum sites and paired arrangements, characterized in that... Cu 2+ Changes in equilibrium Cu at concentrations greater than 0.25 M 2+ The microporous zeolite exhibits a CHA crystal framework structure.
42. A type of small-pore zeolite, wherein, The pores of the microporous zeolite are occupied by at least a portion of the pores by bis-quaternary ammonium cations and by at least a portion of the pores by mono-quaternary ammonium cations, and the microporous zeolite has a CHA crystal framework structure.
43. The small-pore zeolite according to claim 42, wherein, The porous zeolite has a cage-like structure, and the diameter of the spheres that are most likely to be included in the cage-like structure is from 4.4 Å to 15 Å.
44. The small-pore zeolite according to claim 42, wherein, 1% to 99% of the pores are occupied by bis-quaternary ammonium cations, and 99% to 1% of the pores are occupied by mono-quaternary ammonium cations.
45. The small-pore zeolite according to claim 44, wherein, 60% to 40% of the pores are occupied by bis-quaternary ammonium cations, and 40% to 60% of the pores are occupied by mono-quaternary ammonium cations.
46. The small-pore zeolite according to claim 42, wherein, The bisquaternary ammonium cation contains 8 to 20 carbon atoms.
47. The small-pore zeolite according to claim 42, wherein, Each nitrogen atom of the bisquaternary ammonium cation carries four substituents, wherein each substituent is independently selected from the group consisting of alkyl, alkenyl, aryl, aralkyl, and combinations thereof.
48. The small-pore zeolite according to claim 42, wherein, The bisquaternary ammonium cation has a structure represented by formula I: (I) in: Substituents R1, R2, and R3 are each methyl or ethyl; or optionally, two R3 groups are linked to form -(CH2). n -bridge, where n is an integer from 1 to 3; and X is selected from the group consisting of: alkyl, cycloalkyl, alkenyl, aryl, aralkyl and combinations thereof.
49. The small-pore zeolite according to claim 42, wherein, The bisquaternary ammonium cations are N1,N1,N1,N3,N3,N3-hexaethylpropane-1,3-diammonium, N1,N1,N1,N4,N4,N4-hexamethylbutane-1,4-diammonium, N1,N1,N1,N4,N4,N4-hexaethylbutane-1,4-diammonium, (E)-N1,N1,N1,N4,N4,N4-hexamethylbut-2-ene-1,4-diammonium, N1,N1,N1,N5,N5,N5-hexamethylpentane-1,5-diammonium, and (E)-N1,N1,N1,N5. N5,N5-Hexamethylpent-2-ene-1,5-diammonium, N1,N1,N1,N6,N6,N6-Hexamethylhexane-1,6-diammonium (hexamethylammonium), (E)-N1,N1,N1,N6,N6,N6-Hexamethylhexane-2-ene-1,6-diammonium, (2E,4E)-N1,N1,N1,N6,N6,N6-Hexamethylhexane-2,4-diene-1,6-diammonium, N1,N1,N1,N7,N7,N7-Hexamethylheptane-1,7-diammonium, N1,N1,N1,N8,N8 N8-Hexamethyloctane-1,8-diammonium (octamethylammonium), N1,N1,N1,N3,N3,N3-Hexamethylcyclohexane-1,3-diammonium, N1,N1,N1,N3,N3,N3-Hexamethylbicyclo[2.2.1]heptane-1,3-diammonium, N1,N1,N1,N3,N3,N3-Hexamethylbenzene-1,3-diammonium, N1,N1,N1,N4,N4,N4-Hexamethylcyclohexane-1,4-diammonium, N1,N1,N1,N4,N4,N4-Hexamethylbicyclo[2.2.1]heptane -1,4-diammonium, N1,N1,N1,N4,N4,N4-hexamethylbicyclo[2.2.2]octane-1,4-diammonium, N1,N1,N1,N4,N4,N4-hexamethylbenzene-1,4-diammonium, 1,1,4,4-tetramethylpiperazine-1,4-dionium, 1,1,3,3-tetramethylhexahydropyrimidine-1,3-dionium, 1,1'-(1,3-phenylene)bis(N,N,N-trimethylmethaneammonium), 1,1'-(1,4-phenylene)bis(N,N,N-trimethylmethaneammonium), or combinations thereof.
50. The small-pore zeolite according to claim 42, wherein, The bisquaternary ammonium cation is hexamethylammonium or octamethylammonium.
51. The small-pore zeolite according to any one of claims 42-50, wherein, The monoquaternary ammonium cation contains 4 to 14 carbon atoms.
52. The small-pore zeolite according to any one of claims 42-50, wherein, The nitrogen atom of the monoquaternary ammonium cation has four substituents, each of which is independently selected from the group consisting of alkyl, alkenyl, aryl, aralkyl, and combinations thereof.
53. The small-pore zeolite according to any one of claims 42-50, wherein, The monoquaternary ammonium cation has a structure represented by Formula II: (II) in: R1, R2, and R3 are each methyl or ethyl; and R4 is selected from the group consisting of: methyl, ethyl, hydroxyethyl, cyclohexyl, aziridine, heptyl, adamantyl, and phenyl; Alternatively, R3 and R4 together, or R2, R3 and R4 together, can be linked to form a monocyclic or bicyclic system, which can optionally be substituted by one or more methyl or OH groups.
54. The small-pore zeolite according to any one of claims 42-50, wherein, The monoquaternary ammonium cation is tetraethylammonium, 2-hydroxy-N,N,N-trimethylethane-1-ammonium, N,N,N-trimethylcyclohexaneammonium, N,N,N-trimethyladamantane-1-ammonium (TMAda), N,N,N-trimethylbicyclo[2.2.1]heptane-2-ammonium, N,N,N-trimethylphenylammonium, 1,1-dimethylpiperidine-1-onium, 1,1,3,5-tetramethylpiperidine-1-onium, 1-methylquinine-1-onium, 3-hydroxy-1-methylquinine-1-onium, or a combination thereof.
55. The small-pore zeolite according to claim 54, wherein, The monoquaternary ammonium cation is TMAda.
56. The small-pore zeolite according to claim 55, wherein, The bis-quaternary ammonium cation is hexamethylammonium or octamethylammonium, and the mono-quaternary ammonium cation is TMAda.
57. The small-pore zeolite according to any one of claims 41-50, 55 and 56, wherein, The microporous zeolite has a silica-alumina ratio of 6 to 100.
58. The small-pore zeolite according to claim 57, wherein, The pore zeolite has a silica-alumina ratio of 10 to 30.
59. The small-pore zeolite according to claim 58, wherein, The pore zeolite has a silica-alumina ratio in the range of 20 to 30.
60. The small-pore zeolite according to any one of claims 41-50, wherein, The microporous zeolite has a micropore size of less than 75 μm. 2 / g MSA; and at least 450 m 2 / g of ZSA.
61. An effective method for reducing nitrogen oxides (NOx) in exhaust gas. x A selective catalytic reduction catalyst composition comprising a zeolite material according to any one of claims 41-60 promoted by a promoter metal.
62. The selective catalytic reduction catalyst composition according to claim 61, wherein, The amount of the promoter metal is from 1.0 wt% to 10 wt% based on the total weight of the selective catalytic reduction catalyst composition and as a metal oxide.
63. The selective catalytic reduction catalyst composition according to claim 62, wherein, The amount of the accelerator metal present is from 4 wt% to 6 wt%.
64. The selective catalytic reduction catalyst composition according to any one of claims 62-63, wherein, The accelerator metal is selected from iron, copper, and combinations thereof.
65. An effective method for reducing nitrogen oxides (NOx) from engine exhaust gas. x A selective catalytic reduction catalyst article comprising a substrate having a selective catalytic reduction catalyst composition according to any one of claims 61 to 64, the catalyst composition being disposed on at least a portion of the substrate.
66. The selective catalytic reduction catalyst article according to claim 65, wherein, The substrate is a honeycomb substrate.
67. The selective catalytic reduction catalyst article according to claim 66, wherein, The honeycomb substrate is a flow-through substrate or a wall-flow filter.
68. An exhaust gas treatment system comprising a selective catalytic reduction catalyst article according to any one of claims 65 to 67, positioned downstream of and in fluid communication with a lean-burn engine that generates an exhaust gas flow.
69. A method for treating an exhaust gas stream, the method comprising contacting the exhaust gas stream with a selective catalytic reduction catalyst article according to any one of claims 65-67 or an exhaust gas treatment system according to claim 68.
70. A microporous zeolite comprising a CHA framework structure having a C / N ratio in the range of 7 to 15.
Citation Information
Patent Citations
Improvements in and relating to zeolites
GB868846A
AEI zeolite synthesis
US20150118150A1
Crystalline zeolite r
US3030181A
Zeolite SSZ-13 and its method of preparation
US4544538A
Small crystallite zeolite CHA
US6709644B2